Low-temperature pyrolysis enhanced dissociation and waste oil assisted green flotation for the recovery of electrode materials from spent LiCoO2 batteries - Xin-long Li; Xiang-nan Zhu; Guang-liang Wei; Chun-liu Hu; Xiao-tian Zhao; Jing-tao Chen; Wen-hao Gao; Chun-chen Nie; Yong-qiang Zhao; Gu-yue Li (Minerals Engineering, 2026)

EEG emotion recognition based on hierarchical multi-scale graph neural networks - Wenjuan Gu; Junxiang Peng; Shiying Ma; Xin Li; Yang Zou (Cognitive Neurodynamics, 2026)

Nonlinear dynamics of vortex-induced gas entrainment in unbaffled stirred tanks revealed by acoustic emission - Yu Wan; Anqi Li; Yuan Yao; Xin Zhang; Shiliang Gu; Qian Zhang; Guocan Zheng; JinJing Tang; Zuohua Liu (Chemical Engineering Journal, 2026)

Progressive fluorescence amplification of molecular rotors via G-run-length engineering of G-rich DNA scaffolds - Ruo-Yao Cui; Yu-Chao Cao; Yi-Xuan Gu; Ling-Li Zhao; Xu-Yang Shen; Ying Liu; Ying-Lin Zhou; Xin-Xiang Zhang (Analytica Chimica Acta, 2026)

High-efficiency nitrogen removal of ammonium-rich photovoltaic wastewater via a pilot-scale two-stage partial nitritation/anammox system: Long-term performance and techno-economic assessment - Xin Gu; Haixu Shen; Xiang Li; Han Wang; Yayi Wang (Journal of Environmental Chemical Engineering, 2026)

Unlocking efficient Li recovery from spent LiFePO4 batteries at high pulp density: Passivation release mechanism of Fe3+-mediated biochemical synergistic leaching and life cycle assessment - Ziyun Liang; Jinghan Gu; Xin Zhao; Lang Yun; Shenghan Li; Zaiyu Li; Wenyan Liu; Jiali Wang; Yao Wang; Xiaoyu Han (Journal of Environmental Chemical Engineering, 2026)

Improving energy storage capability in BNT-based lead-free ceramics via synergistic design strategy under moderate electric fields - Wenjie Zhou; Xin Wang; Yubin Li; Miao Wang; Long Gu; Fei Yan (Chemical Engineering Journal, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Synergistic Ru/Co sites in N-doped carbon framework for simultaneous electrochemical detection of hydroquinone and catechol - Linyun Zhang; Xun Li; Jiaying Bei; Yao-Yu Pan; Hengjia Wang; Cao Li; Wenling Gu; Xin Luo (Analytica Chimica Acta, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

Structural phase transition–aligned preheating reprograms lipid-derived flavor formation in cooked meat: A case of lamb - Le Xu; Minghui Gu; Yina Chen; Shaobo Li; Xin Li; Cheng Li; Xiaochun Zheng; Li Chen; Dequan Zhang (Food Chemistry, 2026)

Structural ferrous hydroxyl complex unlocks neutral-pH Fenton-like chemistry via multi-pathway ROS generation from nano calcium peroxide - Qian-qian Jia; Rou Liu; Shiyu Wang; Yingmin Liu; Yuwei Gu; Yafei Wang; Yumei Chen; Xiujie Wang; Tongyi Yang; Xin Yan; Li-Zhi Huang (Environmental Research, 2026)

Rapid in-situ enrichment of anammox bacteria from activated sludge via nitrate induction: pilot-scale demonstration and mechanistic insights - Xin Gu; Haixu Shen; Hao Sheng; Xiang Li; Han Wang; Yayi Wang (Environmental Research, 2026)

Spatially heterogeneous impacts of 2D/3D urban form on thermal comfort: insights from urban functional zones - Chunguang Hu; Chunqiang Li; Houbao Fan; Xiaohuan Gu; Xin Li; Jinyu Hu; Peng Zeng; Jianqing Zhao (Energy and Buildings, 2026)

Ion-screening coupled interfacial trapping enabling shuttle-less iodine electrochromics - Weixuan Wang; Hao Li; Jikai Xiang; Yongsheng Liu; Wei Gu; Xin Fu; Yaogang Li; Qinghong Zhang; Chengyi Hou; Kerui Li; Hongzhi Wang (Chemical Engineering Journal, 2026)

The Characterization and Antifungal Efficacy of NJ-62 Protein from Weizmannia coagulans CGMCC 9951 against Ceratocystis fimbriata - Jia Xu; Xiaohan Liu; Xin Li; Ying Wu; Pengyan Li; Shanshan Tie; Pingping Tian; Shaobin Gu (Probiotics and Antimicrobial Proteins, 2026)

Erbin Regulates Neuronal Hyperexcitability and Seizure Susceptibility in Temporal Lobe Epilepsy - Shenglin Wang; Yuping Zhao; Yuansong Zhang; Yaling Li; Yiru Zhang; Yangxi Chen; Xin Xu; Guohui Jiang; Hui Zhang; Haiqing Zhang; Xuefeng Wang; Xiujuan Mi; et al. (Neuroscience Bulletin, 2026)

Oxygen-driven shift from Pb(II) lattice incorporation to reversible surface complexation: Exploiting hydrothermal sludge DOM for high-purity vivianite recovery - Xin Wang; Chaoyue Tai; Lexuan Wang; Yuanyuan Pei; Zhehao Li; Yiyang He; Suyun Xu; Lin Gu; Hanlin Zhang; Haiping Yuan; Haifeng Wen (Water Research, 2026)

Integrated lipidomics and transcriptomics reveal different lipid profiles and metabolic pathways in cultured fats from porcine subcutaneous adipocytes and fibro-adipogenic progenitors - Xin Gu; Qianqian Li; Shiqi Liu; Lay Poh Tan; Teresa G. Valencak; Tizhong Shan (Food Chemistry, 2026)

Deciphering drought resistance in tetraploid Passiflora edulis by integrated transcriptomic and metabolomic profiling - Xin Su; Chiyu Zhou; Sunling Li; Jianzhen Liao; Xiaoyue Zhang; Na Li; Xuesha Gu; Nianhui Cai; Yulan Xu (Food Bioscience, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Developmentally inspired ECM-mimetic hydrogel enhances microenvironment remodeling and functional recovery after spinal cord injury - Biao Wu; Ying Chen; Baizhou Xing; Yu Gu; Changqing Li; Xin Peng; Hai Lu (Chemical Engineering Journal, 2026)

MgI2 immobilized nitrogen and phosphorus co-doped hollow carbon cubes as a multifunctional host for high-performance lithium‑sulfur batteries - Sheng Liang; Cong Li; Zi-Hao Chen; Lei Hu; Xin Liang; Ling-Li Liu; Li-Li Wang; Ning-Ning Zhou; Bin Chen; Wen-Yu Gu; San-E Zhu (Chemical Engineering Journal, 2026)

Biomass-assisted water electrolysis with liquid antimony anode for high efficiency hydrogen evolution - Xin Gu; Mei Zhou; Yidong Jiang; Yuting Li; Chaojun Liu; Jiongyuan Huang; Wenfei Mo; Xiaoyi Liu; Huihuang Fang; Wei Yan; Kongfa Chen; Yixiang Shi; et al. (Chemical Engineering Journal, 2026)

Mapping QTLs with main, epistatic, and QTL × environment effects for secondary seed dormancy using backcross recombinant inbred lines in Brassica napus L. - Fuxia Liu; Lei Liu; Depeng Wu; Xuanxuan Gu; Hexiu Li; Shuwen Bai; Ying Zhou; Yujuan Gu; Tang Tang; Xin Yi; Xiangxiang Zhao (Theoretical and Applied Genetics, 2026)

Apicidin is a key virulence determinant of Fusarium asiaticum in wheat-rice cropping systems - Xin Liu; Kainan Li; Jianbo Qiu; Tao Gao; Yi Shi; Guanghui Shen; Yunyun Zhou; Shilong Hu; Xuanlong Ruan; Jingya Wan; Yin-Won Lee; Qin Gu; et al. (Science China Life Sciences, 2026)

Numerical study on the thermal–hydraulic behaviors within a 19-pin wire-wrapped fuel assembly in lead-based fast reactors under porous blockage conditions based on four-equation model - Yunxiang Li; Runsheng Yang; Yuefeng Guo; Xingkang Su; Yuping Zhou; Jian Hong; Yuxing Liu; Zinan Huang; Xin Su; Youpeng Zhang; WenJun Hu; Long Gu (Annals of Nuclear Energy, 2026)

Synergistic foliar application of zinc and manganese reduces Cd accumulation in rice by enhancing leaf sequestration and modulating Cd transporter gene expression - Chang Li; Hang Zhou; Xia Zhou; Peng Zeng; Lin Song; Lan-Xin Ma; Jiao-Feng Gu (Plant and Soil, 2026)

Multi-level evaluation of sedimentary phosphorus release risk in freshwater water bodies based on dilute-acid extracted phosphorus as indicator - Lanwei Liang; Xin Zhao; Ruilian Guo; Zhenjun Liu; Xiaohan Liu; Xuemei Chen; Yuepeng Yin; Sen Gu; Yang Jiao; Qingman Li (Water Research, 2026)

The domestication-associated WHP10 tandem cluster of amino acid transporter genes enhances whole-plant protein accumulation in maize - Wenhao Li; Youliang Li; Xiang Lin; Ruilin Chen; Wenjing Li; Chong You; Di Chen; Lulu Gao; Xiaoling Li; Shiqi Luo; Yunlong Li; Yuhua Long; et al. (Molecular Plant, 2026)

Z-DNA binding protein 1 mediates heat stress-induced neuronal necroptosis - Jin Deng; Yumeng Gu; Yuchen Li; Miaomiao Wei; Lin Wang; Xin Li (Journal of Thermal Biology, 2026)

A multi-source precipitation blending method combining hydrological model-guided precipitation adjustment and double transfer learning-based data merging - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Jiahua Wei; Yuefei Huang; Shenglong Gu; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

Associations of serum per- and polyfluoroalkyl substances (PFAS) mixture with the risk of chronic diseases: evidence from single‑ , multi-pollutant, and machine learning models - Mei Li; Liting Sheng; Zige Ding; Guangsheng Yu; Yichu Chen; Qitian Chen; Wei Shao; Bingxin Liu; Mulong Du; Dongying Gu; Silu Chen; Junyi Xin; et al. (Archives of Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel calcification-potassium alkali process for zero-waste utilization of low-grade bauxite: Co-production of porous γ-Al₂O₃ and slow-release fertilizer - Qingdong Li; Guozhi Lv; Fangyi Yuan; Bingshen Liu; Xin He; Zhihui Gu; Zhuangzhuang Yun; Tingan Zhang (Journal of Environmental Chemical Engineering, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Hydrogenophaga pseudoflava widely distributed in wastewater treatment plants exhibiting heterotrophic nitrification-aerobic denitrification: From characterization to genomics - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Jia-Ying Li; Ya-Nan Mi; Xin-Yu Gu (Bioresource Technology, 2026)

Cold-Seep Carbonate Factory: Formation Mechanisms, Geochemical Proxies, and Implications for Global Carbon Cycling - Kaiyi Dai; Xiaoming Miao; Yu Gu; Xin Chang; Qing Li; Guangchao Zhuang; Xiting Liu (Journal of Ocean University of China, 2026)

Numerical study on the thermo-hydraulic behaviors of the Directionally-Alternated wire-wrapped fuel assembly in lead-cooled fast reactors based on SSTSAS k-ω-k-ε four-equation model - Yunxiang Li; Runsheng Yang; Yuefeng Guo; Xingkang Su; Yuping Zhou; Jian Hong; Yuxing Liu; Zinan Huang; Xin Su; Youpeng Zhang; WenJun Hu; Long Gu (Annals of Nuclear Energy, 2026)

Sex-specific responses of intestinal health, microbiota composition, and transcriptome profiles in golden pompano (Trachinotus blochii) subjected to hypoxia and reoxygenation - Xiao Kun Wang; Shan Ying Han; Ze Xin Zhong; Zeng Tan Hu; Tian Xiu Li; Yue Gu; Chun Xiu Jin; Tian Jiang; Fei Biao Song; Jian Luo; Jun Long Sun (Frontiers in Marine Science, 2026)
Introduction Driven by global climate change and coastal eutrophication, severe hypoxic events have become a primary environmental stressor in marine ecosystems, posing a critical threat to commercially vital teleosts like the golden pompano ( Trachinotus blochii ). Understanding the dimorphic physiological and microbial responses between sexes under such stress is crucial for developing targeted mitigation strategies. Methods Golden pompano were subjected to hypoxia stress (3.0 ± 0.2 mg/L) for 14 days, followed by restoration of dissolved oxygen to normoxic state (7.0 ± 0.2 mg/L) and cultivation for another 14 days. Subsequently, the histology ( n = 3), digestive enzyme activity ( n = 9), microbial composition ( n = 3), and transcriptome ( n = 3) of intestinal tissue were evaluated. Results Hypoxia induces marked physiological stress and a shift toward intestinal dysbiosis across both genders, manifested by damaged intestinal integrity, oxidative stress, and an increased abundance of opportunistic pathogens (e.g., Spirochaetes ). Although reoxygenation further deteriorates the histological condition of female intestinal tissue, it also triggers more significant molecular and enzyme activity rebound effects compared to males. Moreover, females exhibit significant upregulation of lipid metabolism, antioxidant defense mechanisms, and key signaling pathways, suggesting that they may have adopted a high-energy “compensatory recovery” strategy. Correlation analyses reveal that these microbial shifts are closely linked to host metabolic regulation: beneficial bacteria ( Pseudoalteromonas and Lactococcus ) support sterol transport and signaling homeostasis, while opportunistic taxa ( Brevinema ) negatively impact lipid synthesis. Discussion Our findings reveal a distinct gender dimorphism in the hypoxia and reoxygenation response, providing a theoretical foundation for sex-specific management and nutritional interventions in golden pompano aquaculture.

MDSN-Net: A multi-domain spectral nexus network for underwater accurate fish counting - Jiaming Xin; Tongtong Gu; Zhengmeng Wu; Yiying Wang; Dashe Li; Huanhai Yang (Computers and Electronics in Agriculture, 2026)

Mechanisms of cavitation-induced instability and performance loss in bulb tubular turbines - Xiaotong Song; Zhenggui Li; Shenglong Gu; Chuang Cheng; Meng Liu; Shouchun Liu; Hang Xin; Yanxiong Jiao; Wei Hua (Ocean Engineering, 2026)

Carbon mitigation potential afforded by gridded driving forces in China - Mengqi Fan; Jian Sun; Zezhuang Liu; Yilu Gu; Shengping Li; Hongping He; Xin Liu; Xiaochen Chen; Nan Wei; Xiaofeng Gao (Journal of Environmental Sciences, 2026)

From spent lithium-ion batteries to high-grade “urban mines”: A review of green recovery technologies for strategic metal resources of electrode material - Xiao-tian Zhao; Xiang-nan Zhu; Xin-long Li; Guang-liang Wei; Jing-tao Chen; Chun-liu Hu; Chun-chen Nie; Gu-yue Li; Yong-qiang Zhao (Chemical Engineering Journal, 2026)

A high-performance bimodal sub-nanoporous polyelectrolyte complex membrane for organic solvent nanofiltration constructed by MOF-reinforced nano-unit - Hui-Qian Huo; Bing-Xin Gu; Jin-Lin Wang; Jia-Chen Zhang; Kai Zhang; Ming-Jie Yin; Yan-Li Ji; Quan-Fu An (Chemical Engineering Journal, 2026)

Structural elucidation of an amylopectin from Astragalus membranaceus by integrating selective and quantitative NMR spectra with database matching - Junyin Zhang; Caihong Li; Yu Yang; Yaling Deng; Jiang Xin; Zhongyan Zhu; Xiu Gu; Kaifeng Hu (Carbohydrate Polymers, 2026)

Structural evolution-based ancestral sequence reconstruction of medium-chain alcohol dehydrogenase for efficient synthesis of fused-ring chiral alcohols - Jun Wang; Songyin Zhao; Lehang Li; Manman Zhu; Man Zou; Xin Su; Jie Gu; Yan Xu; Yao Nie (Bioresource Technology, 2026)

First report of mitochondrial genomes in Hydryphantoidea: novel genomes, evolution rate, and gene rearrangement patterns in two water mites (Acari: Hydrachnidia) - Xin-Yao Gu; Ping Li; Hao Zhong; Hai-Tao Li; Jian-Jun Guo; Gang Li; Tian-Xing Jing (Experimental and Applied Acarology, 2026)

Numerical study on the turbulent heat transfer behaviors of the fuel assembly with spacer wires in lead-based fast reactors based on four-equation model - Yunxiang Li; Runsheng Yang; Yuefeng Guo; Xingkang Su; Yuping Zhou; Jian Hong; Yuxing Liu; Zinan Huang; Xin Su; Youpeng Zhang; WenJun Hu; Long Gu (Annals of Nuclear Energy, 2026)

Bone tuberculosis: molecular pathogenesis, diagnostic advances, therapeutic challenges, and emerging strategies for effective management - Xueli Du; Xin Gu; Nan Li; Tao Ji; Wei Fu; Shuai Cao; Meirong Wang; Tao Peng (Archives of Microbiology, 2026)

Evaluation and characterization of aphid (Aphis craccivora) resistance in selected alfalfa genotypes - Xin Jiang; Jing Tian; Gang Li; Guy Smagghe; Zhong-Yi Li; Dao-Chao Jin; Zhou Li; Rui Dong; Xin-Yao Gu (Crop Protection, 2026)

Tonian crustal melting triggered by subduction along the Rodinia periphery: Evidence from the Liujiaping batholith, NW Yangtze Block, South China - Yongcheng Li; Bo Hui; Yunpeng Dong; Shengsi Sun; Zhidong Gu; Yu Zhu; Dengfeng He; Qiwen Dai; Xin Zhu; Shuxuan Yan (Lithos, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Rational design of Ba(II)-cross-linked alginate gel for highly efficient and selective capture of Cu(II) via angular quantum number regulation - Xin Hao; Gaoyuan Gu; Shuyi Yang; Chong Peng; Tao E; Yun Li (Journal of Environmental Chemical Engineering, 2026)

Role of reactive species in the degradation of N-hydroxyphthalimide via the liquid-surface dielectric barrier discharge - Xiao Gu; Bingyan Dong; Zhendong Li; Junwen He; Peixiang Wang; Qing Yang; Dongrui Wang; Xin Li (Journal of Environmental Chemical Engineering, 2026)

Comparative genomics reveals that Bifidobacterium longum subsp. longum BZG4 alleviates constipation in mice via synergistic xylooligosaccharide - YaXin Gu; Qingqiu Ye; Xin Feng; Junzhu Li; Zichen He; Ming Zhang; Yanling Hao; Zhengyuan Zhai (Food Bioscience, 2026)

High-density microfluidic Chip (HD-μChip) for multiplex detection in miniaturized immunoassays - Yiran He; Min Wang; Zhaoxu Luo; Xiaodong Ma; Min Jiang; Yanhua Chen; Jingyi Qin; Yayun Gu; Xin Li; Ying Shi; Hong Wang; Ye Shen; et al. (Chemical Engineering Journal, 2026)

Z-scheme WO3/g-C3N4 assisted DBD-Fenton-like system achieves the decomplexation of SHA-Fe and efficient conversion of Fe3+ - Xiao Gu; Bingyan Dong; Junwen He; Peixiang Wang; Dongrui Wang; Qing Yang; Xin Li (Chemical Engineering Journal, 2026)

Foot Progression Angle Modulates Knee Loading During Walking in Individuals with Flexible Flatfoot - Linxiao Shen; Zhenghui Lu; Xin Li; Zifan Xia; Yufan Xu; Chengyuan Zhu; Yang Song; Xuanzhen Cen; Dong Sun; Gusztáv Fekete; Yaodong Gu (Annals of Biomedical Engineering, 2026)

Discover how interprovincial electricity transmission policies on transforming the regional variations in grid emission factors in China - Boda Xin; Yiyun Yu; Meiyi Li; Yiming Gu; Yahui Zhang; Junfeng Wang (Resources, Conservation and Recycling, 2026)

Mechanisms of 1-methylcyclopropene (1-MCP) in regulating ethylene signal transduction and its role in stress responses: A review - ShiMing Guo; KaiYi Xue; ShaoYan Si; JianWen Gu; Li Liu; WeiLan Yan; Ang Zhang; PengFei Ren; Xin Du (Plant Science, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Preferential N2-transport thin-film composite membrane for energy-efficient CO2 capture - Jin-Lin Wang; Cheng-Gang Jin; Hui-Qian Huo; Bing-Xin Gu; Yue Li; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

Flash joule heating-induced synthesis of biowaste-derived metal-free catalysts for nitrate reduction reaction - Xin Chen; Zhaoyu Wang; Liuhong Yang; Runmiao Yuan; Shuyi Huang; Qinyuan Hu; Xue Wang; Cong Gu; Xiangli Wen; Xi Chen; Hongji Zhang; Dongjian Shi; et al. (Bioresource Technology, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Balancing rice production and greenhouse gas mitigation: assessing the feasible potential of agricultural practices - Qiang Xu; Dicai Ao; Xin Li; Xiangcheng Zhu; Zihao Wang; Yi Yang; Pete Smith; Baojing Gu; Lei Liu; Jinyang Wang; Shuhao Tan; Ziyin Shang; et al. (Resources, Conservation and Recycling, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Erosion control performance of natural geotextiles for slope stabilization - Lihua Li; Shuangdong Liu; Xin Gu; Gang Liu; Xin Zhang; Haowen Xiong (Geotextiles and Geomembranes, 2026)

Integrated metabolomics and transcriptomics reveal differences in fermentation products and the molecular basis among three species of Sanghuang - Yixin Liu; Hongchao Deng; Chen Zhang; Xin Pang; Zhenghua Gu; Moying Li; Liang Zhang (Food Bioscience, 2026)

Efficient nitrogen removal in pilot-scale single-stage partial nitritation/anammox system treating high-ammonia photovoltaic wastewater: System adaptation and potential inhibition - Xin Gu; Xiang Li; Han Wang; Jiaen Wang; Haixu Shen; Yayi Wang (Bioresource Technology, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Denitrification in Hangzhou Bay: The role of nutrient dynamics in a tidal and human-impacted estuarine system - Yuang Guo; Xue Wu; Yangjie Li; Bin Wang; Zhi Yang; Menglu Li; Yixing Zhang; Xin Zhao; Weifang Gu; Zhihao Xu; Hongliang Li; Jianfang Chen (Marine Pollution Bulletin, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Occurrence, distribution, and risk assessment of antibiotics in post-harvest and drained ponds of Sheyang River estuary in Jiangsu Province: Implications for sustainable aquaculture management - Wenqian Shan; Shiya Gu; Wangrong Cui; Xinyun Feng; Xin Song; Jianwei Dong; Hui Xie; Da Li (Journal of Contaminant Hydrology, 2026)

Multiscale analysis reveals cellulose structural features as primary determinants in bamboo (Dendrocalamus farinosus) cell wall recalcitrance - FanQin Yang; Shangmeng Li; Boya Wang; Xiaoyan Gu; Xin Zhao; Wei Fan; Yin Cao; Shanglian Hu (Biomass and Bioenergy, 2026)

Characteristics and outcomes of hospitalized adult patients with respiratory syncytial virus infection in different age groups - Xin Qiao; Jingjing Zhang; Zhinan Zhai; Yuechuan Li; Songtao Gu (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

FTO-Mediated Mitigation of Ferroptosis Occurs in an ACSL4-Dependent Manner in Diabetic Cardiomyopathy - Xin-xin Chen; Yan Gu; Zhe Yin; Yu-tang Li; Zhan-chuan Ma; Wei Wang; Yun-qing Hou; Xiang Wang (Cardiovascular Toxicology, 2026)

Innovative design of CXCR4 cyclic peptide via molecular docking for 99mTc-Labeled SPECT/CT imaging in melanoma - Xianrui Yin; Xin Wang; Chengwei Chen; Shenglan Jia; Wanhong Li; Yihong Wu; Xin Chen; Danling Feng; Wai Ping Cecilia Tsang; Zhihao Han; Yueqing Gu (Analytica Chimica Acta, 2026)

CSN2 of COP9 signalosome underpins high temperature adaptation of the diatom Phaeodactylum tricornutum through regulating protein ubiquitination - Xin Li; Lu Zhou; Wenting Yang; Hong Wang; Xuehua Liu; Songcui Wu; Wenhui Gu; Lijun Wang; Xiujun Xie; Senjie Lin; Qiang Hu; Shan Gao; et al. (Algal Research, 2026)

APOBEC3B-driven mutations negatively regulated by P53 promote tumor progression and immunosuppressive microenvironment in prostate cancer - Yan Guo; Haodi Yu; Xiang Li; Lina Liu; Jing He; Xin Wang; Hui Zhang; Qingyu Zhang; Jing Fu; Ruixue Gu; Hehe Li; Dengfei Xu; et al. (Molecular and Cellular Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A new bisbenzoquinone with cytotoxicity from Chaetomium trilaterale - Xin-Xin Liang; Lei Li; Jia-Yi Zhang; Xin-Yue Zhang; Yi-Kun Feng; Chen Gu; Si-Cheng Jin; Xiang-Guo Meng (Phytochemistry Letters, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Photoaging behavior and neurotoxic effects of shower gel-derived microbeads in Caenorhabditis elegans - Yulun Gu; Yajing Han; Xin Li; Ping Ding; Chaoyi Du; Xiaoxia Chen; Yongqi Jiang; Jinyu Chen; Jingwen Cui; Haibo Chen; Hui Li (Journal of Environmental Management, 2025)

Ultrasonic assisted surfactant/HPAM synergistic purification of highly emulsified oilfield produced water - Jinjun Deng; Zeyu Gu; Xin Zhang; Yanbin Tong; Xiufeng Zhao; Fankun Meng; Zhangshu Wang; Hongsheng Liu; Guoxuan Li (Journal of Environmental Chemical Engineering, 2025)

Characteristics of atmospheric CH4, CO2 and CO at a suburban coastal site in Hong Kong - Wai Ming Chan; Dasa Gu; Ka Fung Leung; Yuchen Mai; Sin Ka Mak; Xin Li; Xiangyunong Cao; Zhenxing Liang; Tsz Ching Tse; Zijie Xu; Hao Sun; Heming Bai; et al. (Atmospheric Environment, 2025)

Seasonal variation and optical properties of brown carbon and nitroaromatic compounds in PM2.5 in the urban area of Beijing - Zhongyi Yin; Xingru Li; Fangkun Wu; Yang Yang; Yuhu Zhang; Zhuohui Yang; Xin Gu; Qing Zhao (Atmospheric Environment, 2025)

Publisher Correction to: Identification of a von Willebrand factor type A protein affecting both grain and flag leaf morphologies in wheat - Chunyun Zhou; Hongchun Xiong; Yong Jia; Huijun Guo; Meiyu Fu; Yongdun Xie; Linshu Zhao; Jiayu Gu; Huiyuan Li; Yuting Li; Peiyong Xin; Jinfang Chu; et al. (Science China Life Sciences, 2025)

Functional Effects of Probiotic Lactiplantibacillus plantarum in Alleviation Multidrug-Resistant Escherichia coli–Associated Colitis in BALB/c Mice Model - Mohamedelfatieh Ismael; Nageena Qayyum; Yaxin Gu; Li Na; Han Haoyue; Muhammad Farooq; Panpan Wang; Qingping Zhong; Xin Lü (Probiotics and Antimicrobial Proteins, 2025)

Genome-wide identification and expression analysis of PP2C gene families in two Chimonanthus species - Xin-Chen He; Jie-Xin Shao; Wei Zou; Shu-Xiao Zhang; Li Zhu; Meng-Cheng Ji; Cui-Hua Gu; Li-Yuan Yang (Genetica, 2025)

Study on the synergistic preparation of mineral potassium silicate fertilizer by hydrothermal leaching of illite under the “Calcification-Potassium alkali” system - Qingdong Li; Guozhi Lv; Xin He; Zhihui Gu; Zhuangzhuang Yun; Xiaolei Zhang; Lingtao Hu; Tingan Zhang (Environmental Geochemistry and Health, 2025)

Chaotic circuit-enhanced electrokinetic leaching of ionic rare earth ores with (NH4)2SO4-MgSO4 compound salt - Yu Wan; Anqi Li; Xin Zhang; Shiliang Gu; Guocan Zheng; Qian Zhan; Jinjing Tang; Changyuan Tao; Jinhui Li; Ping Li; Zuohua Liu (Journal of Cleaner Production, 2025)

Nano-formulated prothioconazole seed coating improves rice bakanae control and seedling establishment via metabolome and respiration modulation - Qizhen Zhang; Xiaofang Liu; Anyu Gu; Xunian Chang; Xin Shi; Xiaolin Li; Jianjun Hao; Pengfei Liu (Chemical Engineering Journal, 2025)

Konjac glucomannan/alginate polysaccharide hydrogel loaded with phosphatidylcholine nanoparticles for hormone-free cultured fat production from porcine fibroblasts - Xin Gu; Shiyuan Hua; Chenchen Li; Xine Shi; Yanbing Zhou; Min Zhou; Tizhong Shan (Carbohydrate Polymers, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

An optimal sequential physical retrieval system for retrieving high-accuracy diurnal atmospheric gases from FY-4B/GIIRS: Theory, algorithm and evaluation - Zhenxing Liang; Dasa Gu; Xin Li; Zijie Xu; Xiangyunong Cao; Heming Bai; Rui Li; Chengxing Zhai; Hui Su; Alexis K.H. Lau (Remote Sensing of Environment, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

The rare-earth metals bio-exaction from Bayan Obo mine by a newly isolated bioleaching functional fugus of Talaromyces pseudofuniculosus - Zaiyu Li; Peng Gao; Xin Zhao; Zaizheng Dong; Jinghan Gu (Journal of Environmental Chemical Engineering, 2025)

Adjusting physiochemical properties of active carbon to increase its capacitive performance on the volumetric basis - Li Dawei; Li Xiaoyan; Zhu Yanjiao; Zhang Zongbo; Qu Xianfeng; Su Tong; Wei Ling; Gu Xin; Li Libin; Yan Caiwen (Desalination, 2025)

Nanoconfinement-engineered ZIF-8/polyelectrolyte gel hybrid membranes for high-efficient antibiotic separation - Wei Chen; Bing-Xin Gu; Yi-Jie Zhang; Hao Zheng; Yan-Li Ji; Quan-Fu An; Cong-Jie Gao (Chemical Engineering Journal, 2025)

Rab5-mediated phagocytosis restricts Spiroplasma eriocheiris infection in crabs through a ubiquitination-dependent mechanism - Yubo Ma; Yu Yao; Xin Yin; Zhenyu Yu; Jing Yan; Yaqin Wang; Wei Gu; Xuguang Li; Jun Zhou; Qingguo Meng (Aquaculture, 2025)

A clean method for alumina production and the coproduction of silicon-potassium compound fertilizer from middle and low grade bauxite ore - Qingdong Li; Guozhi Lv; Renyun Zhang; Zhihui Gu; Xin He; Bingshen Liu; Tingan Zhang (Minerals Engineering, 2025)

Soil mesofauna bacterial diversity: Insights from cultured collembolans, enchytraeids, and mites species - Bo-Wen Liu; Jing Wen; Shuai-Fei Ye; Jia-Jia Gu; Ming-Xin Li; Xiao-Bo Xiong; Zong-Zheng Liang; Hong-Tao Wang (Food Webs, 2025)

Tuning ionic channels in carbon-binder domains of carbon-based electrodes via nonsolvent induced phase separation (NIPS) method - Jiaxin Li; Xin Chen; Yue Cao; Jie Du; Jiajun Gu; Qinglei Liu (Chemical Engineering Journal, 2025)

Red/black phosphorus heterostructure anchored on graphene for lithium-sulfur batteries with accelerated conversion kinetics and improved long-term stability - Xinxin Dong; Xinyu Chen; Xin Tong; Guoqing Liu; Hao Yu; Wei Liu; Huihui Li; Jun Sun; Xiaoyu Gu; Sheng Zhang (Chemical Engineering Journal, 2025)

Landscape Disturbance Effects of the Large-scale Water Storage Activity in the Baihetan Reservoir on the Jinsha River, China - Zhenkui Gu; Chuangchuang Yao; Xin Yao; Xuchao Zhu; Renjiang Li (CATENA, 2025)

A novel multimodal computer-aided diagnostic model for pulmonary embolism based on hybrid transformer-CNN and tabular transformer - Wei Zhang; Yu Gu; Hao Ma; Lidong Yang; Baohua Zhang; Jing Wang; Meng Chen; Xiaoqi Lu; Jianjun Li; Xin Liu; Dahua Yu; Ying Zhao; et al. (Physical and Engineering Sciences in Medicine, 2025)

Null subtraction imaging combined with modified delay multiply-and-sum beamforming for coherent plane-wave compounding - Yijun Xu; Yaoting Yue; Hao Wang; Wenting Gu; Boyi Li; Yaqing Chen; Xin Liu (Medical & Biological Engineering & Computing, 2025)

Screening of Antibiotic-Sensitive Lactic Acid Bacteria (LAB) Associated with the Gut of Penaeus Vannamei and its Application in Shrimp Farming - Yiwen Gu; Xiu Lin; Yanxu Lu; Shuguang Fang; Kun Hu; Xin Ju; Liangzhi Li; Zhi Chen (Current Microbiology, 2025)

Lacticaseibacillus suihuaensis sp. nov., Isolated from Traditional Chinese Pickle - Xin-Yu Zhu; Chun Yan Li; Hao Wang; Chun Tao Gu (Current Microbiology, 2025)

Electrical Detection of Shale Gas Layers Based on Wide-Field Electromagnetic Method - Li-Xin Man; Zhang-Kun Tan; Jian-Chao Jia; Zhi-Wen Gu; Chang-Heng Yu; Xue-Bo Yin (Applied Geophysics, 2025)

Organic sulfur-driven denitrification pretreatment for enhancing autotrophic nitrogen removals from thiourea-containing wastewater: performance and microbial mechanisms - Jiheng Zhu; Xiang Li; Yayi Wang; Xin Gu; Han Wang; Jun Ma; Yong Huang (Water Research, 2025)

Application and identification of monoclonal antibody targeting a novel epitope on p72 protein of African swine fever virus - Yu Dai; Xin Deng; Qi Wang; Ke Yang; Shuqing Yang; Xinran Li; Xinlei Liu; Yuanyuan Yang; Yu Gu; Yi Zheng; Rui Wu (Veterinary Microbiology, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

A multi-modal data-driven meeting room occupancy detection for building energy and spatial optimization - Junyu Chen; Xin Wei; Minxuan Ji; Yan Li; Xiaojun Gu; Juemin Tang (Building and Environment, 2025)

Inactivation effects of slightly acidic electrolyzed water on Cryptosporidium baileyi and Eimeria tenella - Yan Huang; QiuXiang Li; ShiXin Huang; Hongyou Song; Xin Gu; Zhaoguo Chen (Veterinary Parasitology, 2025)

Landform evolution and failure mode of bank collapses controlled by active fault zones and huge water level fluctuations in the Heishui tributary of the Baihetan Reservoir - Chuangchuang Yao; Xin Yao; Zhenkui Gu; Renjiang Li; Kaiyu Ren; Shu Jiang; Li Ma; Fuchu Dai (Geomorphology, 2025)

Exploring the role of carbon source types in trace-level sulfamethoxazole removal and greenhouse gas emissions in AnMBRs - Wanli Yan; Lide Gu; Haoran Li; Jianguo Li; Shikan Zheng; Mingbao Feng; Xin Yu (Environmental Research, 2025)

Clinical biomarkers of perioperative neurocognitive disorder: initiation and recommendation - Jianhui Liu; Cheng Li; Junyan Yao; Lei Zhang; Xuan Zhao; Xin Lv; Zhiqiang Liu; Changhong Miao; Yingwei Wang; Hong Jiang; Weifeng Yu; Tianlong Wang; et al. (Science China Life Sciences, 2025)

Enhancing PPP-RTK performance at low latitudes through mitigation of ionospheric scintillation effects - Xin Li; Bo Wang; Xingxing Li; Shengfeng Gu; Junjie Han (GPS Solutions, 2025)

Dress me an outfit: advanced probiotics hybrid systems for intelligent IBD therapy - Yonglu Li; Yadi Wang; Yapeng Li; Shihai Yan; Xin Gao; Ping Li; Xiaodong Zheng; Qing Gu (Critical Reviews in Food Science and Nutrition, 2025)

Baicalin reduced vandetanib induced myocardial injury by regulating redox balance and NLRP3 inflammasome pathway - Fen Wang; Jianwei Li; Zhixuan Zhang; Guangyi Huang; Xiaodong Zhang; Qian Liu; Wang Xiao; Fengqi Liu; Jialong Sun; Yankui Liu; Yiyi Ma; Ruijuan Zhuang; et al. (Tissue and Cell, 2025)

Discovery of isopentenyl flavonoids with inhibitory activity against hepatocellular carcinoma cells based on DeepSAT - Qing Wang; Ben‐Song Xin; Wen-Long Kou; Li-Na Gao; Gu-Xue Zhang; Yan-Jiao Qiao; Guo‐Dong Yao; Xiao‐Xiao Huang; Shao‐Jiang Song (Phytochemistry, 2025)

Analysis of seepage and hysteresis effect mechanism of unsaturated loess based on resistivity test - Bo Cui; Tianfeng Gu; Jiading Wang; Jiacheng Li; Nannan Fan; Xin Li; Zhijie Song; Min Hao (Journal of Hydrology, 2025)

EHDPP impairs intestinal microbiota homeostasis and induces placental injury through choline mediated gut-placenta axis - Ting Du; Saifei Lei; Zhenyao Huang; Xin Liu; Zhou Jiang; Minlan Lu; Yiyang Zhou; Jiali Yuan; Weiyi Song; Hao Gu; Jing Li (Journal of Hazardous Materials, 2025)

Complete solidification of landfill concentrated leachate using a minimal dosage of mayenite and its reutilization for carbonyl sulfide degradation - Pin Zhou; Xin Li; Dongdong Ge; Nanwen Zhu; Yun Gu; Binglong Zhu; Shouqiang Huang (Journal of Hazardous Materials, 2025)

Comparative study on combustion characteristics of biomass digestate-derived pyrochar and hydrochar: Insights from structural composition and oxygen-containing groups - Haifeng Wen; Jixin Li; Xin Wang; Wei Mao; Yiyang He; Xiao Cao; Haiyan Yang; Junyu Zhang; Suyun Xu; Lin Gu (Fuel, 2025)

Nutrients and metal(loid)s in surface sediments of the Chishui River: A DGT-based assessment of the last natural tributary of the upper Yangtze River (China) - Wei Xia; Tian-Xin Zhang; Xue Li; Yanpeng Gao; Richard W. Jordan; Hong Su; Shi-Jun Jiang; Yang-Guang Gu (Environmental Research, 2025)

Effects of impurities on the syngas fermentation: Mechanism and future perspectives - Jun Ni; Hengfeng Miao; Wanqing Zhang; Xin Chen; Yiheng Tu; Kunlun Yang; Peng Gu; Xueli Ren; Hui Guo; Chunxing Li; Zengshuai Zhang (Bioresource Technology, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Thermal death kinetics of pests in tobacco leaves as influenced by heating rates and life stages - Jinsong Zhang; Xin Ye; Zijun Mo; Hongwei Wang; Xican Gu; Jiaqin Xi; Rui Li; Shaojin Wang (Journal of Stored Products Research, 2025)

Application of a fluorescent probe exhibiting a large stokes shift after the precise detection of hydrazine in plants, foods and living cells - Yan Zhang; Yan Huang; Guiyi Yang; Haotian Xin; Keyi Li; Lei Wang; Shangcong Gu; Baosheng Ren; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2025)

Exposure to polyethylene terephthalate micro(nano)plastics exacerbates inflammation and fibrosis after myocardial infarction by reprogramming the gut and lung microbiota and metabolome - Xin Gu; Zhixuan Zhang; Lin Zhao; Lijie Lu; Xin Lu; Yafei Li; Tianya Gu; Xin Huang; Guangyi Huang; Yan Liang; Haoyu Meng; Baihong Li; et al. (Journal of Hazardous Materials, 2025)

A large language model-based building operation and maintenance information query - Yan Li; Minxuan Ji; Junyu Chen; Xin Wei; Xiaojun Gu; Juemin Tang (Energy and Buildings, 2025)

Achieving efficient phosphorescence of carbon dots via a synergistic enhancement strategy for bright field anti-counterfeiting - Jing Tan; Daiqi Yang; Chunyi Lu; Yi Li; Xingyu Gu; Peng Sha; Songnan Qu; Xin Wang; Lipei Fu; Qijun Li (Chemical Engineering Journal, 2025)

Research on the risk of rainstorm and flood disasters in Songliao basin based on CMIP6 - Jinggang Chu; Wenyu Ouyang; Qian Xin; Xuezhi Gu; Xiaoyang Li; Lei Ye (Natural Hazards, 2025)

Genomics analysis of Vreelandella piezotolerans V23 reveals its role in D-amino acids metabolism - Dan Liu; Tie-Ji Gu; Hou-Qi Wang; Ze-Kun Liu; Meng-Qi Wang; Jing-Li Lü; Xin-Yi Wang; Peng Wang; Chen Wang (Marine Genomics, 2025)

Interfacial structure design enables rapid reaction kinetics for high-voltage NCM 613 cathodes - Yuan Xiao; Rong Gu; Tingting Zheng; Bowen Chang; Qiaoxia Li; Shuaiqi Gong; Xin Wei; Qunjie Xu; Yulin Min (Chemical Engineering Journal, 2025)

Efficient bioleaching of Li from waste lithium–iron phosphate batteries by acidophilic bacterial consortium: Enrichment condition, Li recovery, and brief carbon footprint analysis - Jinghan Gu; Yuanyuan Nie; Zaiyu Li; Kun Yang; Long An; Haiqiang Jiang; Xiaoyu Han; Zhongtian Fu; Xin Zhao (Chemical Engineering Journal, 2025)

Monitoring and numerical analysis of slope deformation in a coal mine in the southwest mountainous regions of China - Xuwen Tian; Xin Yao; Tao Tao; Javed Iqbal; Kaiyu Ren; Zhenkai Zhou; Chuangchuang Yao; Qiyu Li; Lingjing Li; Zhenkui Gu (Natural Hazards, 2025)

Microglia Sing the Prelude of Neuroinflammation-Associated Depression - Qingqing Li; Ying Xie; Jinyi Lin; Miaomiao Li; Ziyan Gu; Tianli Xin; Yang Zhang; Qixia Lu; Yihui Guo; Yanhong Xing; Wuyang Wang (Molecular Neurobiology, 2025)

A genetically modified triradiate strain of Phaeodactylum tricornutum demonstrates considerable advantages in a 60-L photobioreactor - Mengjiao Bao; Wenting Yang; Xin Li; Guihong Yu; Wenhui Gu; Shan Gao; Guangce Wang (Journal of Applied Phycology, 2025)

Prognostic implications and therapeutic opportunities related to CAF subtypes in CMS4 colorectal cancer: insights from single-cell and bulk transcriptomics - Mengke Ma; Jin Chu; Changhua Zhuo; Xin Xiong; Wenchao Gu; Hansheng Li; Midie Xu; Dan Huang (Apoptosis, 2025)

Emission characteristics, environmental impacts and health risk assessment of volatile organic compounds from the typical chemical industry in China - Kaitao Chen; Xin Gu; Min Cai; Weicheng Zhao; Boxuan Wang; Haoran Yang; Xingang Liu; Xingru Li (Journal of Environmental Sciences, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

Carbon-based materials for radar-infrared compatible stealth technology - Xin Tan; Weihua Gu; Zhe Tao; Xiangling Chen; Siyuan Li; Ailin Xia; Guangbin Ji (Chemical Engineering Journal, 2025)

Green revolution gene drives adaptation of Arabidopsis to the extremely high altitude - Xing-Hui Hou; Yong-Chao Xu; Tianshu Sun; Yan-Bo Gong; Xin-Tong Li; Guang-Teng Jin; Yu-Tao Bian; Yi-Ni Liu; Juan Jiang; Xiao-Min Niu; Hongya Gu; Ya-Long Guo (Science China Life Sciences, 2025)

Evaluation of Antibiotic-Sensitive Bacillus Strain as a Potential Probiotic for Enhanced Growth in Penaeus vannamei - Yiwen Gu; Ke Xu; Zhuoran Chen; Yanxu Lu; Shuguang Fang; Kun Hu; Xin Ju; Liangzhi Li; Zhi Chen (Current Microbiology, 2025)

Dry solidification of chloride salts and heavy metals in waste incineration fly ash by mayenite - Xin Li; Dongdong Ge; Nanwen Zhu; Yukai Zong; Shi Cheng; Pin Zhou; Min Jiang; Yun Gu; Shouqiang Huang (Waste Management, 2025)

Intra-urban comparison of hazardous VOCs in Hong Kong: Source apportionment and integrated risk assessment - Xiangyunong Cao; Dasa Gu; Hao Sun; Ka Fung Leung; Yuchen Mai; Xin Li; Wai Ming Chan; Sin Ka Mak; Zhenxing Liang; Wentai Zhang; Yisheng Zhang; Shan Huang; et al. (Sustainable Cities and Society, 2025)

Optimization of pH-responsive microgel for the co-delivery of Weizmannia coagulans and procyanidins to enhance survival rate and tolerance - Qing Zhang; Yujin Yang; Yannan Chen; Shuoshuo Ban; Shaobin Gu; Fang Li; Mengmeng Xue; Jianrui Sun; Xin Li; Shanshan Tie (Food Chemistry, 2025)

Boosting lactic acid photocatalytic synthesis from biomass sugars: The synergistic effect of N-doped carbon dots on ultrathin carbon nitride - Xiao Cao; Xin Wang; Yiyang He; Jixin Li; Haiyan Yang; Pingping Zhang; Songrui Yang; Haixiang Yu; Suyun Xu; Haiping Yuan; Lin Gu (Food Chemistry, 2025)

Microplastics release from infant feeding bottles and milk storage bags - Long Zhao; Yiying Gu; Hua Cai; Xin Xu; Jianguo Yu; Jing Li; Ying Shen; Leiyan Zhu; Yan Jin; Mei Zhang; Ruihua Dong; Bo Chen (Food Control, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Draft Genome of Naganishia uzbekistanensis from a Clinical Pulmonary Infection - Rong-Chen Dai; Xin-Fei Chen; Xin Fan; Li Gu; Li Zhang; Dan Guo; Ying-Chun Xu; Meng Xiao (Mycopathologia, 2025)

Thiolutin Alleviates Cardiotoxic Effects of Doxorubicin by Suppressing NLRP3 Inflammasome in the Mouse Model - Wenyuan Cai; Tingting Teng; Xiaoyan Wang; Baihong Li; Xin Gu; Yafeng Zhou (Cardiovascular Toxicology, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

An in situ reactive zone approach using calcium peroxide for the remediation of benzene and chlorobenzene in groundwater: A field study - Rui Li; Changlong Wei; Zhiwen Tang; Mukhtiar Ali; Zhipan Ma; Bing Li; Ailiang Gu; Xin Song (Journal of Environmental Management, 2025)

Single-cell omics: experimental workflow, data analyses and applications - Fengying Sun; Haoyan Li; Dongqing Sun; Shaliu Fu; Lei Gu; Xin Shao; Qinqin Wang; Xin Dong; Bin Duan; Feiyang Xing; Jun Wu; Minmin Xiao; et al. (Science China Life Sciences, 2025)

Study on the Correlation Between Mechanical Behavior and Electric Potential Response of Flawed Coal Under Dynamic Load - Zesheng Zang; Zhonghui Li; Xiangguo Kong; Yue Niu; Shan Yin; Zhoujie Gu; Xin Zhang (Rock Mechanics and Rock Engineering, 2025)

Combined Effects of Cadmium and Lead on Growth Performance and Kidney Function in Broiler Chicken - Man Zhao; Longqiang Xie; Wenbin Huang; Meiling Li; Xin Gu; Wei Zhang; Jintao Wei; Niya Zhang (Biological Trace Element Research, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

Predicting wheat scab levels based on rotation detector and Swin classifier - Dongyan Zhang; Zhipeng Chen; Hansen Luo; Gensheng Hu; Xin-Gen Zhou; Chunyan Gu; Liping Li; Wei Guo (Biosystems Engineering, 2024)

Enhancing the overturning resistance capacity of high aspect ratio structure through hybrid base isolation and inter-storey isolation - Jingcai Zhang; Yingna Li; Hao Yang; Xin Ji; Lingxi Gu; Wangjingyi Li; Bo Wang; Liang Cheng; Chunwei Zhang (Soil Dynamics and Earthquake Engineering, 2024)

The CpCOR1 gene enhances cold tolerance and antioxidant activity of papaya fruit in response to postharvest chilling stress - Yuwei Nian; Muhammad Muzammal Aslam; Xin Wang; Hui Gu; Wen Li; Yuanzhi Shao (Postharvest Biology and Technology, 2024)

Impact of metals exposure on lung function and serum club cell secretory protein among schoolchildren: A mixture and mediation analysis - Jie Li; Meili Shen; Ting Wang; Xiao Zhang; Wen Gu; Mengmeng Xu; Tongjin Yang; Jie Cui; Xin Xia; Guoping Chen; Siyu Zheng; Haoying Yang; et al. (Journal of Hazardous Materials, 2024)

Corrigendum to “An isolated salt-tolerant Tetragenococcus halophilus 2MH-3 improved the volatile flavor of low-salt fermented fish sauce by regulating the microbial community” [Food Res. Int. 196 (2024) 115052] - Jiarun Han; Shi Hu; Xin Zhao; Jialan Jiang; Qi Wang; Jinfeng Wu; Xilian Zhao; Ping Li; Qing Gu (Food Research International, 2024)

Seasonal variation and origins of C1–C5 alkyl nitrates: A year-long study at a Hong Kong coastal site - Hao Sun; Dasa Gu; Zijie Xu; Xin Feng; Xiangyunong Cao; Yuchen Mai; Xin Li; Ho Wun Lee; Ka Fung Leung; Tsz Ching Tse; Wai Ming Chan; Sin Ka Mak (Atmospheric Environment, 2024)

An isolated salt-tolerant Tetragenococcus halophilus 2MH-3 improved the volatile flavor of low-salt fermented fish sauce by regulating the microbial community - Jiarun Han; Shi Hu; Xin Zhao; Jialan Jiang; Qi Wang; Jinfeng Wu; Xilian Zhao; Ping Li; Qing Gu (Food Research International, 2024)

Quercetin intervention mitigates small intestinal damage and immunologic derangement induced by polystyrene nanoplastics: Insights from multi-omics analysis in mice - Long Zhao; Jianheng Zheng; Yiying Gu; Xin Xu; Jianguo Yu; Jing Li; Shuyu Yang; Bo Chen; Jun Du; Ruihua Dong (Environmental Pollution, 2024)

Reclaiming selenium from water using aluminum-modified biochar: Adsorption behaviors, mechanisms, and effects on growth of wheat seedlings - Xiuyan Wang; Tianxiao Li; Xin Hu; Yuxuan Zhang; Dunhan Zhang; Hanshuo Zhang; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Jun Luo; Bin Gao (Environmental Pollution, 2024)

Tunable sulfur vacancies in amorphous-crystalline AC-Bi2S3-x@C derived from CAU-17 for efficient capture of radioiodine: Comparison of sulfur vacancies in amorphous and crystalline structures - Kai-Wei Chen; Xin-Yu Zhou; Yi-Ting Chen; Xiao-Jun Dai; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ping Mao; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2024)

Spore germination and lactic acid combined treatment: A new processing strategy for the shelf-life extension of instant wet noodles - Qiaozhen Zhang; Fengying Gu; Tian Li; Xin Guo; Yang Li; Manzhu Liang; Feng Wang; Qin Guo; Qiang Wang (International Journal of Food Microbiology, 2024)

Metabolomics combined with intestinal microbiota analysis to reveal the effects of Inonotus hispidus on chronic kidney disease caused by high-protein diet - Xin Pang; Zitao Guo; Long Ao; Yong Huang; Bo Hu; Zhenghua Gu; Yu Xin; Zhongpeng Guo; Rui Zhu; Moying Li; Liang Zhang (Food Bioscience, 2024)

Engineering optimal gold nanorod-loaded hollow mesoporous organosilica nanotheranostics for NIR-II photoacoustic microscopy imaging and tumor synergistic therapy - Xin Li; Xuehan Wang; Hongrui Qiu; Shiying Li; Lik Hang Hugo Tse; Wai-Sum Lo; Kwok-Ho Lui; Haiyu Zhou; Yanjuan Gu; Wing-tak Wong (Chemical Engineering Journal, 2024)

Cascade catalyzed dual-responsive Gold-Ferri “bomb-like” nanoreactors for positive feedback penetrating in sequential targeted triple glioblastoma therapy - Qiyue Wang; Xiaofei Gu; Ji Liu; Yan Zhao; Zhen Li; Shuyan He; Dong Shen; Xiaofei Xin; Yan Shen (Chemical Engineering Journal, 2024)

Identification of a von Willebrand factor type A protein affecting both grain and flag leaf morphologies in wheat - Chunyun Zhou; Hongchun Xiong; Yong Jia; Huijun Guo; Meiyu Fu; Yongdun Xie; Linshu Zhao; Jiayu Gu; Huiyuan Li; Yuting Li; Peiyong Xin; Jinfang Chu; et al. (Science China Life Sciences, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Temperature-dependent development of Carpophilus marginellus Motschulsky, 1858 (Coleoptera: Nitidulidae) and its larval morphological characteristics - Shipeng Shao; Gengwang Hu; Xin Tang; Liangliang Li; Yinghui Wang; Yi Guo; Chengtao Kang; Yundi Gao; Ruonan Zhang; Siqi Liu; Zhiya Gu; Yu Wang (Journal of Stored Products Research, 2024)

Near-infrared and multifunctional fluorescent probe enabled by cyanopyridine cyanine dye for bisulfite recognition and biological imaging - Shangcong Gu; Yan Huang; Xinxin Li; Haotian Xin; Haoran Mu; Yan Zhang; Keyi Li; Guiyi Yang; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2024)

Mechanistic insights into temperature-driven retention and speciation changes of heavy metals (HMs) in ash residues from Co-combustion of refuse-derived fuel (RDF) and red mud - Haifeng Wen; Jingjing Gao; Xin Wang; Yiyang He; Jixin Li; Lin Gu; Ziyu Zhao; Haixiang Yu; Suyun Xu (Journal of Environmental Management, 2024)

The Ciliate Euplotes balteatus Exhibits Removal Capacity upon the Dinoflagellates Karenia mikimotoi and Prorocentrum shikokuense - Jing Li; Haifeng Gu; Vincent J. Lovko; Chen Liang; Xiaodong Li; Xin Xu; Linxuan Jia; Miaohua Jiang; Jinrong Wang; Jianming Chen (Harmful Algae, 2024)

Heterogeneous interface engineering of CoPSe and FePSe3 on open frameworks for boosting highly efficient overall water splitting - Peng Gu; Yidong Song; Yihe Fan; Jin Liu; Xin Meng; Jiahao Xie; Yuxin Li; Zhouguanwei Li; Heyuan Sun; Yao Nie; Jinlong Zou (Chemical Engineering Journal, 2024)

Recent progress on the organelle targeted AlEgens for bioimaging and treatment of diseases - Qihang Ding; Yan Luo; Jun Hu; Shuai Zhang; Wenzhe Zhang; Yuanyuan Feng; Kun Qian; Xin Li; Zhen Cheng; Meijia Gu (Chemical Engineering Journal, 2024)

Soil Total Nitrogen Mediated the Impact of Climatic Factors on Urban Soil Organic Matter Under Different Land Uses - Jia Yang; Abolfazl Masoudi; Hao Li; Yifan Gu; Can Wang; Min Wang; Changhao Wu; Yuanjie Liu; Xin Zhao; Zhijun Yu; Jingze Liu (Journal of Soil Science and Plant Nutrition, 2024)

Spatiotemporal variations and risk assessment of estrogens in the water of the southern Bohai Sea: A comprehensive investigation spanning three years - Shuang Lu; Jing Wang; Baodong Wang; Ming Xin; Chunye Lin; Xiang Gu; Maoshan Lian; Yun Li (Journal of Hazardous Materials, 2024)

Aloe vera and tea polyphenols composite coating delays passion fruit senescence by promoting phenolic and flavonoid accumulation - Yu Wang; Muhammad Muzammal Aslam; Xin Wang; Hui Gu; Wenjun jia; Wen Li; Yuanzhi Shao (Food Research International, 2024)

Discrimination and prediction of Qingzhuan tea storage year using quantitative chemical profile combined with multivariate analysis: Advantages of MRMHR based targeted quantification metabolomics - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Microbiota responses to different brans are conserved within individuals and associated with processing parameters - Zhentao Yao; Ge Zhang; Xin Wang; Jinjun Li; Yuting Qi; Yuanrong Jiang; Jie Gu; Liying Zhu; Xianrong Xu; Xiaoqiong Li (Food Bioscience, 2024)

Moving towards synergistic reductions on PM2.5 and CO2 and its mechanism: A case study of Yangtze River Economic Belt, China - Binjie Gu; Haixia Zhao; Xin Li; Qianqian Zhang (Journal of Geographical Sciences, 2024)

Integration of single-cell and spatial RNA sequencing uncovers spatiotemporal transition of fruit senescence trajectory from exocarp to mesocarp in Pitaya (Hylocereus undatus) - Xinyue Pang; Jiaju Sun; Jingyu Jia; Yuri Trusov; Rahul Chandora; José Ramon Botella; Xin Li; Shaobin Gu (Postharvest Biology and Technology, 2024)

Potential effects of aerosol generation and transmission during bedside endoscope cleaning - Tingting Sheng; Xin Wu; Li Cen; Ye Lu; Chenying Zhou; Qing Gu (Journal of Zhejiang University-SCIENCE B, 2024)

Nitrous oxide emissions and microbial communities variation in low dissolved oxygen and low carbon-to-nitrogen ratio anoxic–oxic wastewater treatment plant - Wanli Yan; Jianguo Li; Lide Gu; Chengsong Ye; Jieping Liang; Jinjin Fu; Shikan Zheng; Xin Yu (Environmental Science and Pollution Research, 2024)

Low-damage fetching method for pepper seedlings based on Res-Unet - Xin Jin; Shuang Chen; Lijun Zhao; Ruoshi Li; Qing Li; Song Gu; Guowei Liu; Jiangtao Ji (Computers and Electronics in Agriculture, 2024)

Discovery of abundant shock-induced metallic lead nanograins in lunar zirconolite - Ai-Cheng Zhang; Hao-Xuan Sun; Tian-Ran Trina Du; Jia-Ni Chen; Li-Xin Gu (Geochimica et Cosmochimica Acta, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Comprehensive review of microbial production of medium-chain fatty acids from waste activated sludge and enhancement strategy - Xin Gu; Jing Sun; Tong Wang; Jia Li; Han Wang; Jialin Wang; Yayi Wang (Bioresource Technology, 2024)

Electric Potential Response Characteristics of Coal Under Stress Wave Loading - Zesheng Zang; Zhonghui Li; Xin Zhang; Xiangguo Kong; Zhoujie Gu; Shan Yin; Yue Niu (Natural Resources Research, 2024)

Monitoring Yanwan deep-seated toppling deformation with the impact of water-level fluctuation by SAR observations - Kaiyu Ren; Renjiang Li; Xin Yao; Xiaoming Zhao; Li Ma; Chuangchuang Yao; Shu Jiang; Zhenkui Gu; Zhenkai Zhou (Landslides, 2024)

Identification of SNPs and candidate genes associated with growth using GWAS and transcriptome analysis in Coilia nasus - Yue Yu; Shi-Ming Wan; Shuang-Meng Zhang; Jun-Qi Liu; Ai-Li Sun; Yao Wang; Yong-Fu Zhu; Shu-Xin Gu; Ze-Xia Gao (Aquaculture, 2024)

The combined effects of azoxystrobin and different aged polyethylene microplastics on earthworms (Eisenia fetida): A systematic evaluation based on oxidative damage and intestinal function - Xin Bao; Zijian Wang; Li Liu; Dengwei Wang; Yuntong Gu; Long Chen; Xiaojun Chen; Zhiyuan Meng (Science of The Total Environment, 2024)

Smart Breeding Platform: A web-based tool for high-throughput population genetics, phenomics, and genomic selection - Huihui Li; Xin Li; Peng Zhang; Yingwei Feng; Junri Mi; Shang Gao; Lele Sheng; Mohsin Ali; Zikun Yang; Liang Li; Wei Fang; Wensheng Wang; et al. (Molecular Plant, 2024)

Oligotrophic characteristics and genomic analysis of the Rhodoligotrophos defluvii lm1T isolated from activated sludge - Chengjiao Yu; Xin Sui; Changfeng Miao; Boya Liang; Pengfei Gu; Qiang Li (International Biodeterioration & Biodegradation, 2024)

A finite element-based dynamic simulation method for modeling shield-ground interactions: 3D numerical simulations with comparison to physical experiments - Guansi Gu; Zixin Zhang; Xin Huang; Yun Li; Qinghua Lei (Computers and Geotechnics, 2024)

Target mediated bioreaction to engineer surface vacancy effect on Bi2O2S nanosheets for photoelectrochemical detection of FEN1 - Jiangwei Hu; Xin Gao; Mengmeng Gu; Yuanyuan Sun; Yuming Dong; Guang-Li Wang (Analytica Chimica Acta, 2024)

Research on automatic recognition of active landslides using InSAR deformation under digital morphology: A case study of the Baihetan reservoir, China - Yang Liu; Xin Yao; Zhenkui Gu; Renjiang Li; Zhenkai Zhou; Xinghong Liu; Shu Jiang; Chuangchuang Yao; Shangfei Wei (Remote Sensing of Environment, 2024)

Clay minerals/sodium alginate/polyethylene hydrogel adsorbents control the selective adsorption and reduction of uranium: Experimental optimization and Monte Carlo simulation study - Jingjie Yang; Jianan Nie; Liang Bian; Jingmei Zhang; Mianxin Song; Fei Wang; Guocheng Lv; Li Zeng; Xiaobin Gu; Xin Xie; Peng Zhang; Qing Song (Journal of Hazardous Materials, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Fullerenol mitigates ischemia/reperfusion-induced kidney injury - Hao Wang; Junsong Guo; Xuefeng Ding; Ying Li; Hui Xu; Xinyi Tian; Xin Tan; You Liao; Haiyang Jiang; Jing Wei; Haijun Peng; Zhanjun Gu; et al. (Chemical Engineering Journal, 2024)

Cruise observation of ambient volatile organic compounds over Hong Kong coastal water - Hao Sun; Dasa Gu; Xin Feng; Zhe Wang; Xiangyunong Cao; Mingyao Sun; Zhi Ning; Penggang Zheng; Yuchen Mai; Zijie Xu; Wai Ming Chan; Xin Li; et al. (Atmospheric Environment, 2024)

Non-enzymatic Detection of Uric Acid in Serum and Urine by Fluorescent and Visual Dual-Mode Sensor Based on 3-aminophenylboric Acid Functionalized Carbon Dots - Xin Li; Guoqing Chen; Anqi Hu; Yi Xiong; Taiqun Yang; Chaoqun Ma; Lei Li; Hui Gao; Chun Zhu; Yamin Wu; Jiao Gu; Hui Wu; et al. (Journal of Fluorescence, 2024)

STS ⅡA inhibited angiogenesis of lung adenocarcinoma by activating FOXO3 to inhibit CXCL1/STAT3/VEGF pathway - Bu Wang; Fang Zou; Gu Xin; Bao-Li Xiang; Jian-Qing Zhao; Sheng-Fang Yuan; Xiu-Long Zhang; Zhi-Hua Zhang (Toxicon, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Research on the intelligent layout method of ship multi-deck cabins based on improved SLP and GMBOA - Yunlong Wang; Yujie Gu; Xin Zhang; Kai Li; Guan Guan (Ocean Engineering, 2024)

Kinematic response analysis of a three-dimensional lifeboat water entry based on smoothed particle hydrodynamics - Ming-Yuan Li; Jie Cui; Xin Chen; Chang-Jun Gu; Bright Masvaya (Ocean Engineering, 2024)

Carbon sinks/sources' spatiotemporal heterogeneity and their spatial response to economic-social factors in relatively developed regions: A case of China's coastal area - Xin Li; Haixia Zhao; Binjie Gu; Yijiang Chen (Journal of Environmental Management, 2024)

Insight into the effect of cultivar and altitude on the identification of EnshiYulu tea grade in untargeted metabolomics analysis - Dan Zou; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Xian-Chun Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Development of crop growing from the late Yangshao to early Longshan period in the Zhengluo region of central China: phytolith evidence from the Shuanghuaishu site - Binggui Sun; Yuzhang Yang; Wanfa Gu; Weiya Li; Qilong Cui; Xin Zhou; Juzhong Zhang (Vegetation History and Archaeobotany, 2024)

Chronic Pb exposure impairs learning and memory abilities by inhibiting excitatory projection neuro-circuit of the hippocampus in mice - Rong-Xin Zou; Xiaozhen Gu; Chenqing Huang; Hui-Li Wang; Xiang-tao Chen (Toxicology, 2024)

An intrusion and environmental effects of man-made silver nanoparticles in cold seeps - Kelei Zhu; Jiawei Liu; Mingyu Zhao; Lulu Fu; Zengfeng Du; Fanqi Meng; Lin Gu; Peiyu Liu; Yan Liu; Chaoqun Zhang; Xin Zhang; Jinhua Li (Science of The Total Environment, 2024)

Rational design of a cross-type HPV vaccine through immunodominance shift guided by a cross-neutralizing antibody - Zhiping Wang; Daning Wang; Jie Chen; Fei Gao; Yanan Jiang; Chengyu Yang; Ciying Qian; Xin Chi; Shuyue Zhang; Yujie Xu; Yihan Lu; Jingjia Shen; et al. (Science Bulletin, 2024)

UHPLC-QTOF-MS-based untargeted metabolomic authentication of Chinese red wines according to their grape varieties - Xiao-Li Yin; Zhi-Xin Peng; Yuan Pan; Yi Lv; Wanjun Long; Hui-Wen Gu; Haiyan Fu; Yuanbin She (Food Research International, 2024)

Comparative analysis of key precursors and metabolites involved in flavor formation of different rapid-fermented Chinese fish sauces based on untargeted metabolomics analysis - Jiarun Han; Jialan Jiang; Xin Zhao; Xilian Zhao; Tao Kong; Ping Li; Qing Gu (Food Chemistry, 2024)

Flexible catabolism of monoaromatic hydrocarbons by anaerobic microbiota adapting to oxygen exposure - Zhiming Wu; Xin Yu; Yanhan Ji; Guiping Liu; Ping Gao; Lei Xia; Pengfa Li; Bin Liang; Shiri Freilich; Lifeng Gu; Wenjing Qiao; Jiandong Jiang (Journal of Hazardous Materials, 2024)

Characterization of a Bacillus velezensis strain as a potential biocontrol agent against soft rot of eggplant fruits - Xiaoyun Zhang; Yu Xin; Junyi Wang; Solairaj Dhanasekaran; Qingrong Yue; Faping Feng; Xiangyu Gu; Bo Li; Lina Zhao; Hongyin Zhang (International Journal of Food Microbiology, 2024)

Natural polymer/wide-bandgap inorganic hybrids for visible-light-driven CO2 photoreduction: Unraveling the multiple effects of interfacial chemical bonding - Jing Li; Yingxi Xiao; Songting Gu; Kejun Wu; Xi Zhao; Xiaoyang Zhao; Junmin Nan; Xin Xiao (Chemical Engineering Journal, 2024)

Symmetrical distribution of P sites on thorn assembled Graphite carbon nitride microtube for photocatalytic conversion of CO2 - Luoming Zhang; Xin Zhao; Mingyang Liu; Qi Li; Yihang Yin; Xuena Ma; Huiquan Gu; Baojiang Jiang (Chemical Engineering Journal, 2024)

A chemical derivatization-based pseudotargeted liquid chromatography-tandem mass spectrometry method for sensitive and high coverage determination of bile acids in human serum - Xin Xiong; Xunke Gu; Xiaona Li; Keke Jia; Yuan Wei; Rongsheng Zhao (Analytica Chimica Acta, 2024)

Simultaneous separation and analysis of multiple doxorubicin hydrochloride liposomes forms in serum by circular nonuniform electric field gel electrophoresis - Peijie Xie; Xinlei Yang; Zakia Fatima; Ruilin Yang; Huaze Sun; Yuhang Xing; Xin Xu; Jingkai Gu; Lu Liu; Donghao Li (Analytica Chimica Acta, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Elucidating applied voltage on the fate of antibiotic resistance genes in microbial electrolysis cell: Focusing on its transmission between anolyte and biofilm microbes - Shiguang Liu; Zengshuai Zhang; Peng Gu; Kunlun Yang; Xin Huang; Manman Li; Hengfeng Miao (Science of The Total Environment, 2023)

Artificial light at night, MRI-based measures of brain iron deposition and incidence of multiple mental disorders - Jianbo Jin; Wenxing Han; Teng Yang; Zhihu Xu; Jin Zhang; Ru Cao; Yuxin Wang; Jiawei Wang; Xin Hu; Tiantian Gu; Fan He; Jing Huang; et al. (Science of The Total Environment, 2023)

A study on the value of carbon compensation in the Huai River basin based on land use from 2000 to 2020 - Haihong Song; Xin Zhang; Jinlong Zou; Liyuan Gu; Yifan Li; Jingnan Tang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

A new mechanistic insight into the association between environmental perfluorooctane sulfonic acid (PFOS) exposure and attention deficit and hyperactivity disorder (ADHD)-like behavior - Miao Zhang; Xueyan Gu; Liu Wu; Nannan Wan; Yu Liu; Zaijun Xin; Tianbing Chen; Shuai Liu; Mingqi Li; Mi Deng; Qiyu Wang (NeuroToxicology, 2023)

Study on Impact Dynamic Behavior and Failure Characteristics of Coal based on True Triaxial Split–Hopkinson Pressure Bar Experiments - Rongxi Shen; Zhoujie Gu; Zhentang Liu; Enlai Zhao; Zesheng Zang; Xin Zhou; Xiaoliang Li; Wei Liu; Xi Wang (Natural Resources Research, 2023)

Strain Rate Effect and Mechanical Constitutive Model of Coal Samples Under Dynamic Load - Zhoujie Gu; Rongxi Shen; Zhentang Liu; Xin Zhou; Xiaoliang Li; Zesheng Zang; Li Zhang; Wei Liu; Xi Wang (Natural Resources Research, 2023)

Clinical comprehensive evaluation of direct oral anticoagulants for patients with atrial fibrillation in China - Chi Zhang; Zhi-Chun Gu; Er-Li Ma; Bing-Long Liu; Mang-Mang Pan; Jia Wang; Xin Wang; Bin Wu; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Dry and wet seasonal variations of the sediment fungal community composition in the semi-arid region of the Dali River, Northwest China - Xin Chen; Guoce Xu; Ping Xiong; Jianbo Peng; Kang Fang; Shun Wan; Bin Wang; Fengyou Gu; Jing Li; Haijing Xiong (Environmental Science and Pollution Research, 2023)

Pentachlorophenol exposure induced neurotoxicity by disrupting citrulline metabolism in larvae and adult zebrafish - Yi Zhang; Wenzheng Li; Jun Zhu; Xin Qian; Wenlong Pei; Zhenyang Gu; Qian Wu; Zhan Zhang; Lei Li (Toxicology and Applied Pharmacology, 2023)

Nanoscale evidence of zircon-coffinite-xenotime solid solution observed by atom probe tomography - Wenhao Zhao; Bi-Wen Wang; Li-Xin Gu; Xu Tang; Yu Liu; Muhammad Awais; Xiao-Chi Liu; Xian-Hua Li; Rong Hu; Qiu-Li Li (Chemical Geology, 2023)

Dynamic quantification of on-road emissions in Hong Kong: Impact from traffic congestion and fleet composition variation - Xin Li; Dasa Gu; Tilman Leo Hohenberger; Yik Him Fung; Jimmy C.H. Fung; Alexis K.H. Lau; Zhenxing Liang (Atmospheric Environment, 2023)

Theoretical calculation-guided engineering of Fe-Mn based dual-center single-atom catalysts for synergistic tumor therapy - Xueyang Fang; Decai Yang; Xianlin Wu; Kwok-Ho Lui; Xin Li; Wai-Sum Lo; Chenxi Li; Yuanyuan Zhang; Guohui Nie; Lijun Jiang; Yanjuan Gu; Bin Zhang; et al. (Chemical Engineering Journal, 2023)

Organic Carbon Deposition on the Inner Shelf of the East China Sea Constrained by Sea Level and Climatic Changes Since the Last Deglaciation - Mingyu Zhang; Xiting Liu; Fangjian Xu; Anchun Li; Yu Gu; Xin Chang; Guangchao Zhuang; Kaidi Zhang; Naishuang Bi; Houjie Wang (Journal of Ocean University of China, 2023)

Genetic diversity, antibiotic resistance, and virulence characteristics of Staphylococcus aureus from raw milk over 10 years in Shanghai - Jiewen Huang; Wengang Zhang; Bingqing Sun; Qin Jiang; Ying Cao; Jun Shang; Yu Zhang; Xin Gu; Chao Lv; Chaoyi Guo; Min Li; Hui Li; et al. (International Journal of Food Microbiology, 2023)

Precooking treatments affect the sensory and tensile properties of autoclaved recooked noodles via moisture distribution and protein structure - Xin Guo; Fengying Gu; Yang Li; Qiaozhen Zhang; Runrun Hu; Bo Jiao; Feng Wang; Qiang Wang (Food Chemistry, 2023)

Trehalose metabolism targeting as a novel strategy to modulate acid tolerance of yeasts and its application in food industry - Zhongpeng Guo; Moying Li; Zitao Guo; Rui Zhu; Yu Xin; Zhenghua Gu; Liang Zhang (Food Microbiology, 2023)

Expression and functional analysis of ace1 and ace2 reveal their differential roles in larval growth and insecticide sensitivity in Spodoptera frugiperda (J. E. Smith, 1797) - Jie Gao; Li-Feng Gong; Huan-Huan Wang; Rui Zhao; Xing Xiao; Xin-Yao Tian; Bo Li; Pei Liang; Xi-Wu Gao; Shao-Hua Gu (Journal of Pest Science, 2023)

Enhancing wheat Fusarium head blight detection using rotation Yolo wheat detection network and simple spatial attention network - Dong-Yan Zhang; Han-Sen Luo; Tao Cheng; Wei-Feng Li; Xin-Gen Zhou; Wei-Guo; Chun-Yan Gu; Zhihua Diao (Computers and Electronics in Agriculture, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Comparative analysis of volatile compounds and microbial community succession in Chinese fish sauce: Three typical types of fast-fermented fish sauces - Jiarun Han; Jialan Jiang; Tao Kong; Xilian Zhao; Xin Zhao; Ping Li; Qing Gu (Food Bioscience, 2023)

Modification of green space on the associations between long-term road traffic noise exposure and incident intracerebral hemorrhage: A prospective cohort study - Tiantian Gu; Teng Yang; Jiawei Wang; Xin Hu; Zhihu Xu; Yuxin Wang; Jianbo Jin; Jin Zhang; Tianfeng He; Guoxing Li; Jing Huang (Environmental Research, 2023)

Suppression of Microglial ERO1a Alleviates Inflammation and Enhances the Efficacy of Rehabilitative Training After Ischemic Stroke - Jing Ren; Yuan Lv; Qiuyan Tian; Li Sun; Po Miao; Xiaofeng Yang; Li-Xiao Xu; Chen-Xi Feng; Mei Li; Qin Gu; Xing Feng; Xin Ding (Molecular Neurobiology, 2023)

Seismic performance and damage properties of flexure–shear critical RC columns with various loading cycles - Qin Zhang; Ming-Hui Chen; Wen-Jie Li; Xiang-Lin Gu; Jin-Xin Gong (Bulletin of Earthquake Engineering, 2023)

Impact of Cold Spells on Ischemic Stroke Severity and Clinical Outcomes in Tianjin, China - Juanjuan Xue; Chanjuan Wei; Xiaoshuang Xia; Xuemei Qi; Yumeng Gu; Zhongyan Wang; Suqin Han; Lin Wang; Xin Li (Journal of Meteorological Research, 2023)

Bacterial community assembly and antibiotic resistance genes in soils exposed to antibiotics at environmentally relevant concentrations - Zeyou Chen; Wei Zhang; Anping Peng; Yike Shen; Xin Jin; Robert D. Stedtfeld; Stephen A. Boyd; Brian J. Teppen; James M. Tiedje; Cheng Gu; Dongqiang Zhu; Yi Luo; et al. (Environmental Microbiology, 2023)
Understanding how bacterial community assembly and antibiotic resistance genes (ARGs) respond to antibiotic exposure is essential to deciphering the ecological risk of anthropogenic antibiotic pollution in soils. In this study, three loam soils with different land management (unmanured golf course, dairy‐manured pasture, and swine‐manured cornfield) were spiked with a mixture of 11 antibiotics at the initial concentration of 100 and 1000 μg kg −1 for each antibiotic and incubated over 132 days, mimicking a scenario of pulse disturbance and recovery in soils, with unspiked soil samples as the control treatment. The Infer Community Assembly Mechanisms by Phylogenetic‐bin‐based null model (iCAMP) analysis demonstrated that drift and dispersal limitation contributed to 57%–65% and 16%–25%, and homogeneous selection 12%–16% of soil bacterial community assembly. Interestingly, antibiotic exposure to 1000 μg kg −1 level significantly increased the contribution of drift to community assembly, largely due to the positive response from Acidobacteria‐6 in the golf course and pasture soils and from Chthoniobacteraceae in the cornfield soil to the antibiotic exposure. However, ARG abundance and diversity in the three soils exhibited antibiotics‐independent temporal fluctuations, but were associated with the changes in soil bacterial communities over time. This study provides the first insight into the relative contributions of different bacterial community assembly processes in soils upon antibiotic exposure at environmentally relevant concentrations.

Numerical study of wedge entry in still water and waves using smoothed particle hydrodynamics methods - Jie Cui; Chang-Jun Gu; Xin Chen; Ming-Yuan Li; Bright Masvaya (Ocean Engineering, 2023)

Climate Informed Non-stationary Modeling of Extreme Precipitation in China - Chi Zhang; Xuezhi Gu; Lei Ye; Qian Xin; Xiaoyang Li; Hairong Zhang (Water Resources Management, 2023)

Network prediction of surgical complication clusters: a prospective multicenter cohort study - Xiaochu Yu; Peng Wu; Zixing Wang; Wei Han; Yuguang Huang; Shijie Xin; Qiang Zhang; Shengxiu Zhao; Hong Sun; Guanghua Lei; Taiping Zhang; Luwen Zhang; et al. (Science China Life Sciences, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Effect of ammonia on the soot surface characteristics in ammonia/ethylene co-flow diffusion flames - Feng Zhang; Shuanglong Li; Qianqian Liu; Jingyun Sun; Xin Wei; Mingyan Gu; Yang Wang; Xiangyong Huang (Fuel, 2023)

Effects of drying methods on bioactive components of Ganoderma lucidum fermented whole wheat in products & in vitro digestive model - Yang Li; Fengying Gu; Xin Guo; Qiaozhen Zhang; Runrun Hu; Ling Qin; Qiang Wang; Feng Wang (Food Research International, 2023)

Rapidly analyzing of ingredients during chewing and processing of areca nut using feature-based molecular networking - Moying Li; Xin Pang; Zhenghua Gu; Zitao Guo; Yu Xin; Liang Zhang (Food Chemistry, 2023)

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

Loss of ndrg2 Function Is Involved in Notch Activation in Neuromast Hair Cell Regeneration in Zebrafish - Xin Wang; Xiaodong Gu; Cheng Wang; Yingzi He; Dong Liu; Shan Sun; Huawei Li (Molecular Neurobiology, 2023)

Pentacyclic triterpenoids from spikes of Prunella vulgaris L. with thyroid tumour cell cytostatic bioactivities - Xiu-Qin Zheng; Lei-Xin Song; Zhu-Zhen Han; Ying-Bo Yang; Yi Zhang; Li-Hua Gu; Li Yang; Gui-Xin Chou; Zheng-Tao Wang (Natural Product Research, 2023)

Effects of different fermentation synergistic chemical treatments on the performance of wheat straw as a nursery substrate - Jun Li; Chao Xu; Xin Zhang; Zhiyun Gu; Hongliang Cao; Qiaoxia Yuan (Journal of Environmental Management, 2023)

Novel insights from protein degradation: Deciphering the dynamic evolution of biogenic amines as a quality indicator in pork during storage - Minghui Gu; Cheng Li; Yuanyuan Su; Li Chen; Shaobo Li; Xin Li; Xiaochun Zheng; Dequan Zhang (Food Research International, 2023)

Synergies of Ru/Co nanoparticles and Co single atoms active sites toward efficient electrocatalysis of oxygen reduction reaction for Zn-Air battery - Xin Luo; Songlin Zhao; Zhen Luo; Shentian Li; Xiao Zhao; Qie Fang; Xiaoqian Wei; Hengjia Wang; Canglong Wang; Zhihong Zhu; Wenling Gu (Chemical Engineering Journal, 2023)

The status of the global food waste mitigation policies: experience and inspiration for China - Guohui Shen; Ziqi Li; Tiannuo Hong; Xin Ru; Kunzhen Wang; Yanting Gu; Juan Han; Yanzhi Guo (Environment, Development and Sustainability, 2023)
Food waste has become a significant challenge faced by the community with a shared future for mankind, and it has also caused a considerable impact on China's food security. Scholars across disciplines, international organizations, and especially policymakers are increasingly interested in food waste. Policies are seen as a powerful factor in reducing food waste, but current research on related policies is more scattered. This paper summarizes and analyzes the experiences of food waste policy development and implementation by systematically reviewing the studies on food waste reduction policies. The results of this paper's analysis show that current global food waste policies are focused at the national strategic level, with approaches such as legislation, food donation, waste recycling, awareness and education, and data collection. At the same time, we find that the current experience of developed countries in policy formulation and implementation is beneficial for policy formulation in developing countries. And taking China as an example, we believe that developing countries can improve food waste policies in the future by improving legislation, guiding the development of food banks, promoting social governance, and strengthening scientific research projects. These policies will all contribute strongly to global environmental friendliness. In addition, we discuss some of the factors that influence the development of food waste policies and argue that in the future, more consideration needs to be given to the effects of policy implementation and that case studies should focus more on developing countries. This will contribute to the global sustainable development process.

Copper-catalyzed radical trifluoromethylalkynylation of unactivated alkenes with terminal alkynes - Yang-Qing Ren; Chang-Jiang Yang; Zhong-Liang Li; Qiang-Shuai Gu; Lin Liu; Xin-Yuan Liu (Journal of Fluorine Chemistry, 2023)

Yak bone collagen-derived anti-inflammatory bioactive peptides alleviate lipopolysaccharide-induced inflammatory by inhibiting the NF-κB signaling pathway and nitric oxide production - Yuliang Yang; Lingyu Zhu; Zitao Guo; Chunyu Liu; Bo Hu; Moying Li; Zhenghua Gu; Yu Xin; Haiyan Sun; Yanming Guan; Liang Zhang (Food Bioscience, 2023)

Characteristics and source origin analysis of halogenated hydrocarbons in Hong Kong - Xiangyunong Cao; Dasa Gu; Xin Li; Ka Fung Leung; Hao Sun; Yuchen Mai; Wai Ming Chan; Zhenxing Liang (Science of The Total Environment, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

A contrast of Pb(II), Cd(II), and Cu(II) toxicities to Aspergillus niger through biochemical, morphological, and genetic investigations - Lin Zhang; Xin Yang; Sensen Li; Lingyi Tang; Tianyi Chen; Tingting Gu; Genqiang Chen; Geoffrey Michael Gadd; Zhen Li (Journal of Hazardous Materials, 2023)

A critical review on the interaction of polymer particles and co-existing contaminants: Adsorption mechanism, exposure factors, effects on plankton species - Xiaying Xin; Bing Chen; Min Yang; Sichen Gao; Hongjie Wang; Wenwen Gu; Xixi Li; Baiyu Zhang (Journal of Hazardous Materials, 2023)

CaFe-layered double hydroxide corn straw biochar reduced heavy metal uptake by Brassica campestris L. and Ipomoea aquatic F.: Rhizosphere effects and oxidative stress alleviation - Fangming Yu; Tiantian Gu; Jiayu Wei; Chijian Tang; Songying Li; Yuyuan Chen; Yanlan Su; Kehui Liu; Jiangming Ma; Xin Liang; Yi Li (Journal of Environmental Management, 2023)

Application of a novel and green temperature-responsive deep eutectic solvent system to simultaneously extract and separate different polar active phytochemicals from Schisandra chinensis (Turcz.) Baill - Xin-Yu Yan; Zi-Hui Cai; Peng-Quan Zhao; Jian-Dong Wang; Li-Na Fu; Qi Gu; Yu-Jie Fu (Food Research International, 2023)

Synthesis, Structure and Near Infrared Fluorescence Property of a New Nd-MOF Based on a Triangular Benzylamine Ligand - Hui Li; Hongsheng Wang; Wen Gu; Xin Liu (Journal of Fluorescence, 2023)

Comprehensive profiling of the distribution, risks and priority of pharmaceuticals and personal care products: A large-scale study from rivers to coastal seas - Shuang Lu; Jing Wang; Baodong Wang; Ming Xin; Chunye Lin; Xiang Gu; Maoshan Lian; Yun Li (Water Research, 2023)

Metagenomics analysis reveals potential pathways and drivers of piglet gut phage-mediated transfer of ARGs - Yalu Ji; Hengyu Xi; Zhen Zhao; Qiujie Jiang; Chong Chen; Xinwu Wang; Fengyang Li; Na Li; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; et al. (Science of The Total Environment, 2023)

Damming has changed the migration process of microplastics and increased the pollution risk in the reservoirs in the Shaying River Basin - Jiachen Shen; Xu Gu; Run Liu; Hongyu Feng; Dianpeng Li; Yan Liu; Xufei Jiang; Ge Qin; Shuqing An; Ning Li; Xin Leng (Journal of Hazardous Materials, 2023)

Comprehensive study of energy and water exchange over the Tibetan Plateau: A review and perspective: From GAME/Tibet and CAMP/Tibet to TORP, TPEORP, and TPEITORP - Yaoming Ma; Tandong Yao; Lei Zhong; Binbin Wang; Xiangde Xu; Zeyong Hu; Weiqiang Ma; Fanglin Sun; Cunbo Han; Maoshan Li; Xuelong Chen; Jiemin Wang; et al. (Earth-Science Reviews, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Driving effects of dynamic geomorphologic environments on gravitational erosion hazards: a case of the Baihetan drainage area of the Jinsha River, China - Zhenkui Gu; Xin Yao; Chenggang Li; Xuchao Zhu (Bulletin of Engineering Geology and the Environment, 2023)

De Novo Transcriptome Analysis of the Early Hybrid Triploid Loach (Misgurnus anguillicaudatus) Provides Novel Insights into Fertility Mechanism - Ziyu Zhou; Gu Shan; Xin Li; Wenxuan Guo; Kexin Ma; Yueyao Yang; Yifan Li; Yunbang Zhang; He Zhou; Xiaojuan Cao (Fishes, 2023)
As a new freshwater aquaculture product, triploid loaches (Misgurnus anguillicaudatus) are characterized by fast growth, high-quality meat, high edibility, high resistance to disease, and sterility. In this study, a natural tetraploid loach (4n = 100) (♀) was crossed with a diploid loach (2n = 50) (♂), thus creating the hybrid triploid loach (3n = 75). The histological observations of triploid offspring and diploid controls at 4 days post-hatching (dph), 15dph, 22dph, and 50dph showed that most of the hybrid triploid loaches were abortive in the early gonad differentiation process. To explore its fertility mechanism, through transcriptome analyses of triploid offspring and diploid controls at four periods, 10 differentially expressed genes related to the early fertility mechanism were identified: amh, hormad1, rec8, h2b, plvap, zp3, h2a, nrb0b1, ddx4, and esr2. According to the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of DEGs, two pathways were identified that are closely related to the early fertility mechanism at 50dph: the estrogen signaling pathway and steroid biosynthesis. The findings laid a foundation for further exploration of their molecular inhibition mechanism in hybrid triploid loaches.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

Easy regulation of chitosan-based hydrogel microstructure with citric acid as an efficient buffer - Keyi Li; Xueting Yang; Xin Dong; Hongyan Cao; Shujuan Zhuang; Xiangling Gu (Carbohydrate Polymers, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Soil health assessment in the Yangtze River Delta of China: Method development and application in orchards - Yan Cao; Xin Li; Xiaoyong Qian; Hairong Gu; Jinwen Li; Xiaohua Chen; Genxiang Shen (Agriculture, Ecosystems & Environment, 2023)

An Optimization Model for Ship Speed Based on Maneuvering Control - Xin Li; Yiqing Gu; Xiang Fan; Kang Zou; Xianrui Hou (Journal of Marine Science and Engineering, 2022)
The increasing frequency of serious environmental issues and high fuel costs have necessitated better energy efficiency in the shipping industry. According to a report by the International Maritime Organization (IMO), ship speed optimization has huge potential. This paper introduces an optimization model of ship speed based on maneuvering control. The trajectory tracking theory and sliding mode control method are applied to simulate the control load of a ship. The propeller mode and rudder mode are used to calculate the corresponding rotating speed of the propeller, the rudder angle and the energy consumption. The accuracy and robustness of the maneuvering control model are validated in a still water scenario and a level 5 sea state scenario. On this basis, a particle swarm optimization (PSO) algorithm is applied to determine the best speed combination. The result shows that sailing at a constant speed is the most energy-saving strategy in still water. Moreover, due to the effects of wind, waves and currents, ships should sail faster when the sea is calm and slower when the sea is rough. These results are consistent with the actual experiences of a captain.

Infrared Radiation and Acoustic Emission of Damage Evolution and Failure Precursory for Water-Bearing Coal - Tiancheng Shan; Zhonghui Li; Xin Zhang; Yue Niu; He Tian; Quancong Zhang; Zesheng Zang; Zhoujie Gu; Chao Cai; Chen Liu (Rock Mechanics and Rock Engineering, 2022)

P2X7-mediated alteration of membrane fluidity is associated with the late stages of age-related macular degeneration - Candace Drysdale; Keunha Park; Kirstan A. Vessey; Xin Huang; Emily Caruso; Yihan Li; Joelyn Wong; James S. Wiley; Erica Fletcher; Robyn H. Guymer; Ben J. Gu (Purinergic Signalling, 2022)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Identification of mutational signature for lung adenocarcinoma prognosis and immunotherapy prediction - Sainan Zhang; Mengyue Li; Yilong Tan; Juxuan Zhang; Yixin Liu; Wenbin Jiang; Xin Li; Haitao Qi; Lefan Tang; Ran Ji; Wenyuan Zhao; Yunyan Gu; et al. (Journal of Molecular Medicine, 2022)

First Detection and Molecular Identification of Entamoeba bovis in Farm-Raised Sika Deer from Anhui Province, China - Xin-chao Liu; Qi Ren; Jie Guo; Dong-qian Chen; Qiao-qiao Li; Xin-yu Luo; You-fang Gu; Wen-chao Li (Acta Parasitologica, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

MiRNA let-7i promotes radiation-induced pulmonary epithelial-mesenchymal transition by targeting IL-10 - Shenghui Zhou; Xin Liang; Zewen Sun; Xueping Li; Jiaojiao Zhu; Zhihua Yang; Xiujie Pan; Yilong Wang; Yongqing Gu; Maoxiang Zhu (Genome Instability & Disease, 2022)

Two new alkaloids from Tibetan medicine of Hypecoum leptocarpum - Bo Sun; Israa Assani; Chun-Gu Wang; Mu-Xuan Wang; Ling-Fei Liu; Yan Li; Ge Yan; Yun-Ruo Yang; Zhi Chen; Zhi-Xin Liao (Natural Product Research, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Xylomexicanins K-N: limonoids from the leaves and twigs of Xylocarpus granatum - Shao-Jing Li; Li-Kang Zhao; Jin-Jun Chen; Chun-Hua Zhou; Xin-Li Huang; Yi-Bing Wu; Françoise Sauriol; Yu-Cheng Gu; Hiromasa Kiyota (Natural Product Research, 2022)

Identifying the Mechanism of Toppling Deformation by InSAR : A Case Study in Xiluodu Reservoir, Jinsha River - Yifei Zhu; Xin Yao; Leihua Yao; Zhenkai Zhou; Kaiyu Ren; Lingjing Li; Chuangchuang Yao; Zhenkui Gu (Landslides, 2022)

Bioaccessibility and Toxicity Assessment of Polycyclic Aromatic Hydrocarbons in Two Contaminated Sites - Huihui Cao; Xiaona Li; Changsheng Qu; Meng Gao; Hu Cheng; Ni Ni; Shi Yao; Yongrong Bian; Chenggang Gu; Xin Jiang; Yang Song (Bulletin of Environmental Contamination and Toxicology, 2022)

Omics analyses indicate sdhC/D act as hubs of early response of E. coli to antibiotics - Lei Chen; Ying Wu; Qianwen Zhao; Chao Tang; Xinyue Pang; Shaobin Gu; Xin Li (Archives of Microbiology, 2022)

The relationship between short-term PM2.5 exposure and outpatient visits for acne vulgaris in Chongqing, China: a time-series study - Xiang Li; Lai-Xin Zhou; Li-Li Yang; Xiao-Long Huang; Nan Wang; Yue-Gu Hu; En-Jie Tang; Hua Xiao; Yu-Meng Zhou; Ya-Fei Li; Yuan-Gang Lu; Tong-Jian Cai (Environmental Science and Pollution Research, 2022)

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Discovery of a Natural Product with Potent Efficacy Against SARS-CoV-2 by Drug Screening - Daixi Li; Cheng Wang; Shaobo Wang; Aamir Mehmood; Jiang Gu; Xin Cheng; Peiqin Chen; JingFei Qiu; Jinghong Zhao; Junping Wang; Dongqing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Genetic Diversity and Population Structure of Gynaephora qinghaiensis in Yushu Prefecture, Qinghai Province Based on the Mitochondrial COI Gene - Haizhen Wang; Xin Zhong; Huafeng Lin; Shaosong Li; Jiequn Yi; Guren Zhang; Xin Liu; Li Gu (Biochemical Genetics, 2021)

Dammarane-type saponins from Gynostemma pentaphyllum and their cytotoxicities - Wei-Ye Cui; Yulian Jin; Hui Liu; Ma-Li Zu; Xin-Fang Zhai; Ce Yang; Yu-Long Gu; Yong Cheng; Xiang-Lan Piao (Natural Product Research, 2021)

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Changes in Brain Functional Network Connectivity in Adult Moyamoya Diseases - Gaoxing Zheng; Yu Lei; Yuzhu Li; Wei Zhang; Jiabin Su; Xiaoying Qi; Liang Chen; Xin Zhang; Yuxiang Gu; Yuguo Yu; Ying Mao (Cognitive Neurodynamics, 2021)

Mapping of geomorphic dynamic parameters for analysis of landslide hazards: A case of Yangbi river basin on the upper Lancang-Mekong of China - Zhen-kui Gu; Xin Yao; Chuang-chuang Yao; Cheng-gang Li (Journal of Mountain Science, 2021)

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Evaluation of common genetic variants in vitamin E-related pathway genes and colorectal cancer susceptibility - Qiuyi Zhang; Yixuan Meng; Mulong Du; Shuwei Li; Junyi Xin; Shuai Ben; Zhengdong Zhang; Dongying Gu; Meilin Wang (Archives of Toxicology, 2021)

Genetic variants in Hippo signalling pathway-related genes affect the risk of colorectal cancer - Hengyang Shen; Yixuan Meng; Tao Hu; Shuwei Li; Mulong Du; Junyi Xin; Dongying Gu; Meilin Wang; Zan Fu (Archives of Toxicology, 2021)

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Food-grade expression of nattokinase in Lactobacillus delbrueckii subsp. bulgaricus and its thrombolytic activity in vitro - Chen Li; Zaihui Du; Shaoqing Qi; Xin Zhang; Miaoshu Wang; Yangping Zhou; Haiqiang Lu; Xinxi Gu; Hongtao Tian (Biotechnology Letters, 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Predicting postmortem interval based on microbial community sequences and machine learning algorithms - Ruina Liu; Yuexi Gu; Mingwang Shen; Huan Li; Kai Zhang; Qi Wang; Xin Wei; Haohui Zhang; Di Wu; Kai Yu; Wumin Cai; Gongji Wang; et al. (Environmental Microbiology, 2020)
Summary Microbes play an essential role in the decomposition process but were poorly understood in their succession and behaviour. Previous researches have shown that microbes show predictable behaviour that starts at death and changes during the decomposition process. Research of such behaviour enhances the understanding of decomposition and benefits estimating the postmortem interval (PMI) in forensic investigations, which is critical but faces multiple challenges. In this study, we combined microbial community characterization, microbiome sequencing from different organs (i.e. brain, heart and cecum) and machine learning algorithms [random forest (RF), support vector machine (SVM) and artificial neural network (ANN)] to investigate microbial succession pattern during corpse decomposition and estimate PMI in a mouse corpse system. Microbial communities exhibited significant differences between the death point and advanced decay stages. Enterococcus faecalis , Anaerosalibacter bizertensis , Lactobacillus reuteri , and so forth were identified as the most informative species in the decomposition process. Furthermore, the ANN model combined with the postmortem microbial data set from the cecum, which was the best combination among all candidates, yielded a mean absolute error of 1.5 ± 0.8 h within 24‐h decomposition and 14.5 ± 4.4 h within 15‐day decomposition. This integrated model can serve as a reliable and accurate technology in PMI estimation.

Analysis of an improved workflow of endoscope reprocessing for bedside endoscopic diagnosis and treatment on COVID-19 patients - Qing Gu; Hua-fen Wang; Ying Fang; Ye Lu; Zhe Shen; Yan Wang; Xin Wu; Li Cen; Yi-shu Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Three new ɑ-pyrone derivatives induced by chemical epigenetic manipulation of Penicillium herquei , an endophytic fungus isolated from Cordyceps sinensis - Da-Le Guo; Ling Qiu; Dan Feng; Xin He; Xiao-Hua Li; Zhi-Xing Cao; Yu-Cheng Gu; Ling Mei; Fang Deng; Yun Deng (Natural Product Research, 2020)

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

Selenate Reduction and Selenium Enrichment of Tea by the Endophytic Herbaspirillum sp. Strain WT00C - Xiao Xu; Wei Cheng; Xin Liu; Heng You; Guitai Wu; Kunming Ding; Xiuliang Tu; Lanfang Yang; Youpin Wang; Yadong Li; Haoshuang Gu; Xingguo Wang (Current Microbiology, 2020)

Mycorrhizal impacts on root trait plasticity of six maize varieties along a phosphorus supply gradient - Xin-Xin Wang; Hongbo Li; Qun Chu; Gu Feng; Thomas W. Kuyper; Zed Rengel (Plant and Soil, 2020)

New cold-resistant, seedless grapes developed using embryo rescue and marker-assisted selection - Peipei Zhu; Bao Gu; Peiying Li; Xin Shu; Xing Zhang; Jianxia Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Genetic variants in circTUBB interacting with smoking can enhance colorectal cancer risk - Ke Zhang; Shuwei Li; Dongying Gu; Kaili Xu; Rui Zheng; Junyi Xin; Yixuan Meng; Shuai Ben; Haiyan Chu; Zhengdong Zhang; Yongqian Shu; Mulong Du; et al. (Archives of Toxicology, 2020)

Antioxidative and Probiotic Activities of Lactic Acid Bacteria Isolated from Traditional Artisanal Milk Cheese from Northeast China - Yunjia Shi; Xingyang Cui; Shanshan Gu; Xin Yan; Rui Li; Shuang Xia; Hongyan Chen; Junwei Ge (Probiotics and Antimicrobial Proteins, 2019)

Does Biochar Induce Similar Successions of Microbial Community Structures Among Different Soils? - Yang Song; Xiaona Li; Min Xu; Wei Jiao; Yongrong Bian; Xinglun Yang; Chenggang Gu; Fang Wang; Xin Jiang (Bulletin of Environmental Contamination and Toxicology, 2019)

Quantitative division of succession and spatial patterns among different stand developmental stages in Changbai Mountains - Zhi-wen Gong; Xin-gang Kang; Li Gu (Journal of Mountain Science, 2019)

Adhesion and Colonization of the Probiotic Lactobacillus rhamnosus Labeled by Dsred2 in Mouse Gut - Chen Li; Tingting Bei; Zhihua Niu; Xin Guo; Miaoshu Wang; Haiqiang Lu; Xinxi Gu; Hongtao Tian (Current Microbiology, 2019)

Formation mechanism and movement processes of the Aizigou paleolandslide, Jinsha River, China - Tong Shen; Yunsheng Wang; Zhiquan Huang; Jia Li; Xin Zhang; Wenzheng Cao; Jin Gu (Landslides, 2019)

Ultrafiltration for the Determination of Cu Complexed with Dissolved Organic Matters of Different Molecular Weight from a Eutrophic River, China - Anding Li; Yan Zhang; Beihai Zhou; Kailing Xin; Yingnan Gu; Weijie Xu; Jie Tian (Bulletin of Environmental Contamination and Toxicology, 2018)

Identification of a Splicing Mutation in ITPR1 via WES in a Chinese Early-Onset Spinocerebellar Ataxia Family - Li Wang; Ying Hao; Peng Yu; Zhenhua Cao; Jin Zhang; Xin Zhang; Yuanyuan Chen; Hao Zhang; Weihong Gu (The Cerebellum, 2018)

Identification of Strategic Residues at the Interface of Antigen–Antibody Interactions by In Silico Mutagenesis - Lu Xin; Hai Yu; Qiyang Hong; Xingjian Bi; Xiao Zhang; Zhiqing Zhang; Zhibo Kong; Qingbing Zheng; Ying Gu; Qinjian Zhao; Jun Zhang; Shaowei Li; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Recent advances in rapid pathogen detection method based on biosensors - Ying Chen; Zhenzhen Wang; Yingxun Liu; Xin Wang; Ying Li; Ping Ma; Bing Gu; Hongchun Li (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

In Vitro-In Vivo Predictive Dissolution-Permeation-Absorption Dynamics of Highly Permeable Drug Extended-Release Tablets via Drug Dissolution/Absorption Simulating System and pH Alteration - Zi-qiang Li; Shuang Tian; Hui Gu; Zeng-guang Wu; Makafui Nyagblordzro; Guo Feng; Xin He (AAPS PharmSciTech, 2018)

Selenylation modification: enhancement of the antioxidant activity of a Glycyrrhiza uralensis polysaccharide - Ke-Xun Lian; Xiao-Qing Zhu; Jie Chen; Gang Liu; Xin-Li Gu (Glycoconjugate Journal, 2018)

Investigation of glucose fluctuations by approaches of multi-scale analysis - Yunyun Lai; Zhengbo Zhang; Peiyao Li; Xiaoli Liu; YiXin Liu; Yi Xin; Weijun Gu (Medical & Biological Engineering & Computing, 2018)

Porcine teschovirus 2 induces an incomplete autophagic response in PK-15 cells - Yuanxing Gu; Yingshan Zhou; Xinfeng Shi; Yongping Xin; Ying Shan; Cong Chen; Tong Cao; Weihuan Fang; Xiaoliang Li (Archives of Virology, 2018)

Human placenta-derived mesenchymal stem cells loaded on linear ordered collagen scaffold improves functional recovery after completely transected spinal cord injury in canine - Sufang Han; Zhifeng Xiao; Xing Li; Huan Zhao; Bin Wang; Zhixue Qiu; Zhi Li; Xin Mei; Bai Xu; Caixia Fan; Bing Chen; Jin Han; et al. (Science China Life Sciences, 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China - Yi-Wei Peng; Xue-Xiang Gu; Peng-Rui Lv; Yong-Mei Zhang; Wen-Bin Cheng; Xin-Li Wang (International Geology Review, 2017)

Preparation and In Vitro Evaluation of a MRI Contrast Agent Based on Aptamer-Modified Gadolinium-Loaded Liposomes for Tumor Targeting - Lan-Xin Zhang; Kun-Feng Li; Huan Wang; Meng-Jie Gu; Li-Si Liu; Zhuo-Zhao Zheng; Nan-Yin Han; Zhen-Jun Yang; Tian-Yuan Fan (AAPS PharmSciTech, 2017)

Curcumin attenuates surgery-induced cognitive dysfunction in aged mice - Xiang Wu; Huixin Chen; Chunhui Huang; Xinmei Gu; Jialing Wang; Dilin Xu; Xin Yu; Chu Shuai; Liping Chen; Shun Li; Yiguo Xu; Tao Gao; et al. (Metabolic Brain Disease, 2017)

Expression and functional activity of bitter taste receptors in primary renal tubular epithelial cells and M-1 cells - Jie Liang; Fuxue Chen; Fu Gu; Xin Liu; Feng Li; Dongshu Du (Molecular and Cellular Biochemistry, 2017)

Genetic characterization of H9N2 avian influenza virus in plateau pikas in the Qinghai Lake region of China - Yan Yan; Jin-Yan Gu; Zhuang-Chuan Yuan; Xin-Yu Chen; Zeng-Kui Li; Jing Lei; Bo-li Hu; Li-Ping Yan; Gang Xing; Min Liao; Ji-Yong Zhou (Archives of Virology, 2017)

Lentiviral Vector-Induced Overexpression of RGMa in the Hippocampus Suppresses Seizures and Mossy Fiber Sprouting - Ling Chen; Baobing Gao; Min Fang; Jie Li; Xiujuan Mi; Xin Xu; Wei Wang; Juan Gu; Bo Tang; Yanke Zhang; Zhihua Wang; Ao Zhan; et al. (Molecular Neurobiology, 2017)

The mobile monitoring of black carbon and its association with roadside data in the Chinese megacity of Shanghai - Xiao-ning Lei; Ji-wei Bian; Guang-li Xiu; Xiao-feng Hu; Xin-sheng Gu; Qing-gen Bian (Environmental Science and Pollution Research, 2017)

Biodegradation of the Herbicide 2,4-Dichlorophenoxyacetic Acid by a New Isolated Strain of Achromobacter sp. LZ35 - Zhen-Yuan Xia; Long Zhang; Yan Zhao; Xin Yan; Shun-Peng Li; Tao Gu; Jian-Dong Jiang (Current Microbiology, 2017)

Comparative genomic analysis of isoproturon‐mineralizing sphingomonads reveals the isoproturon catabolic mechanism - Xin Yan; Tao Gu; Zhongquan Yi; Junwei Huang; Xiaowei Liu; Ji Zhang; Xihui Xu; Zhihong Xin; Qing Hong; Jian He; Jim C. Spain; Shunpeng Li; et al. (Environmental Microbiology, 2016)
Summary The worldwide use of the phenylurea herbicide, isoproturon (IPU), has resulted in considerable concern about its environmental fate. Although many microbial metabolites of IPU are known and IPU‐mineralizing bacteria have been isolated, the molecular mechanism of IPU catabolism has not been elucidated yet. In this study, complete genes that encode the conserved IPU catabolic pathway were revealed, based on comparative analysis of the genomes of three IPU‐mineralizing sphingomonads and subsequent experimental validation. The complete genes included a novel hydrolase gene ddhA , which is responsible for the cleavage of the urea side chain of the IPU demethylated products; a distinct aniline dioxygenase gene cluster adoQTA1A2BR , which has a broad substrate range; and an inducible catechol meta ‐cleavage pathway gene cluster adoXEGKLIJC . Furthermore, the initial mono‐ N ‐demethylation genes pdmAB were further confirmed to be involved in the successive N ‐demethylation of the IPU mono‐ N ‐demethylated product. These IPU‐catabolic genes were organized into four transcription units and distributed on three plasmids. They were flanked by multiple mobile genetic elements and highly conserved among IPU‐mineralizing sphingomonads. The elucidation of the molecular mechanism of IPU catabolism will enhance our understanding of the microbial mineralization of IPU and provide insights into the evolutionary scenario of the conserved IPU‐catabolic pathway.

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

An improved biofilter to control the dissolved organic nitrogen concentration during drinking water treatment - Huining Zhang; Li Gu; Bing Liu; Huihui Gan; Kefeng Zhang; Huixia Jin; Xin Yu (Environmental Science and Pollution Research, 2016)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Efficacy and safety of quetiapine extended release monotherapy in bipolar depression: a multi-center, randomized, double-blind, placebo-controlled trial - Huafang Li; Niufan Gu; Hongyan Zhang; Gang Wang; Qingrong Tan; Fude Yang; Yuping Ning; Honggeng Zhang; Zheng Lu; Xiufeng Xu; Jianguo Shi; Chengge Gao; et al. (Psychopharmacology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Comprehensive phenotypic analysis and quantitative trait locus identification for grain mineral concentration, content, and yield in maize (Zea mays L.) - Riliang Gu; Fanjun Chen; Bingran Liu; Xin Wang; Jianchao Liu; Pengcheng Li; Qingchun Pan; Jordon Pace; Ayaz-Ali Soomro; Thomas Lübberstedt; Guohua Mi; Lixing Yuan (Theoretical and Applied Genetics, 2015)

Generation and characterization of Brassica rapa ssp. pekinensis – B. oleracea var. capitata monosomic and disomic alien addition lines - AI XIA GU; SHU XING SHEN; YAN HUA WANG; JIAN JUN ZHAO; SHU XIN XUAN; XUE PING CHEN; XIAO FENG LI; SHUANG XIA LUO; YU JING ZHAO (Journal of Genetics, 2015)

Sphingomonas chloroacetimidivorans sp. nov., a chloroacetamide herbicide-degrading bacterium isolated from activated sludge - Kai Chen; Qing Chen; Guo-Xiang Wang; Hai-Yan Ni; Jian He; Xin Yan; Jin-Gang Gu; Shun-Peng Li (Antonie van Leeuwenhoek, 2015)

High-Level S100A6 Promotes Metastasis and Predicts the Outcome of T1–T2 Stage in Clear Cell Renal Cell Carcinoma - Xiangjun Lyu; Hongzhao Li; Xin Ma; Xintao Li; Yu Gao; Dong Ni; Donglai Shen; Liangyou Gu; Baojun Wang; Yu Zhang; Xu Zhang (Cell Biochemistry and Biophysics, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Erratum to: Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Role of cosubstrate and bioaccessibility played in the enhanced anaerobic biodegradation of organochlorine pesticides (OCPs) in a paddy soil by nitrate and methyl-β-cyclodextrin amendments - Mao Ye; Mingming Sun; Ni Ni; Yinwen Chen; Zongtang Liu; Chengang Gu; Yongrong Bian; Feng Hu; Huixin Li; Fredrick Orori Kengara; Xin Jiang (Environmental Science and Pollution Research, 2014)

Icariin-Mediated Inhibition of NF-κB Activity Enhances the In Vitro and In Vivo Antitumour Effect of 5-Fluorouracil in Colorectal Cancer - De-Bing Shi; Xin-Xiang Li; Hong-Tu Zheng; Da-Wei Li; Guo-Xiang Cai; Jun-Jie Peng; Wei-Lie Gu; Zu-Qing Guan; Ye Xu; San-Jun Cai (Cell Biochemistry and Biophysics, 2014)

Interferon-γ produced by tumor-infiltrating NK cells and CD4+ T cells downregulates TNFSF15 expression in vascular endothelial cells - Yi Lu; Xin Gu; Li Chen; Zhi Yao; Juan Song; Xiulong Niu; Rong Xiang; Tao Cheng; Zhihai Qin; Weimin Deng; Lu-Yuan Li (Angiogenesis, 2014)

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

Assessment of wheat variety stability using SSR markers - Li Xin Wang; Hong Bo Li; Tie Cheng Gu; Li Hua Liu; Bin Shuang Pang; Jun Qiu; Chang Ping Zhao (Euphytica, 2014)

Selection of Antiviral Peptides Against Mink Enteritis Virus Using a Phage Display Peptide Library - Qingming Zhang; Yuping Wang; Qun Ji; Jingmin Gu; Shanshan Liu; Xin Feng; Changjiang Sun; Yingying Li; Liancheng Lei (Current Microbiology, 2013)

GSA: a GPU-accelerated structure similarity algorithm and its application in progressive virtual screening - Xin Yan; Qiong Gu; Feng Lu; Jiabo Li; Jun Xu (Molecular Diversity, 2012)

Construction of Escherichia coli strains producing l-serine from glucose - Yu Li; Gu-Kui Chen; Xin-Wei Tong; Hui-Tu Zhang; Xiao-Guang Liu; Yi-Han Liu; Fu-Ping Lu (Biotechnology Letters, 2012)

Down-modulation of TNFSF15 in ovarian cancer by VEGF and MCP-1 is a pre-requisite for tumor neovascularization - Weimin Deng; Xin Gu; Yi Lu; Chao Gu; Yangyang Zheng; Zhisong Zhang; Li Chen; Zhi Yao; Lu-Yuan Li (Angiogenesis, 2012)

Trigonella arcuata-associated rhizobia—an Ensifer (Sinorhizobium) meliloti population adapted to a desert environment - Yu Rong He; Jing Yu Wang; En Tao Wang; Gu Feng; Yue Li Chang; Xin Hua Sui; Wen Xin Chen (Plant and Soil, 2011)

Isotopic niche overlap of two planktivorous fish in southern China - Gang Chen; Zaohe Wu; Binhe Gu; Dongyan Liu; Xin Li; Yang Wang (Limnology, 2011)

Removal of dichloroacetic acid from drinking water by using adsorptive ozonation - Li Gu; Xin Yu; Jinli Xu; Lu Lv; Qing Wang (Ecotoxicology, 2011)

Accumulation of ions during seed development under controlled saline conditions of two Suaeda salsa populations is related to their adaptation to saline environments - Xin Li; Xiaodong Zhang; Jie Song; Hai Fan; Gu Feng; Baoshan Wang (Plant and Soil, 2011)

Preliminary Evidence that Copper and Zinc Inhibits the Dissipation of Synthetic Pyrethroid in Red Soil - Xiao-zhi Gu; Lei Zhang; Gang-ya Zhang; Cheng-xin Fan; Li Chen (Water, Air, & Soil Pollution, 2010)

Molecular Modeling and Affinity Determination of scFv Antibody: Proper Linker Peptide Enhances Its Activity - Xin Gu; Xiaoling Jia; Jiannan Feng; Beifen Shen; Ying Huang; Shusheng Geng; Yingxun Sun; Yugang Wang; Yan Li; Mian Long (Annals of Biomedical Engineering, 2010)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Antibiotic‐resistance profile in environmental bacteria isolated from penicillin production wastewater treatment plant and the receiving river - Dong Li; Min Yang; Jianying Hu; Jing Zhang; Ruyin Liu; Xin Gu; Yu Zhang; Zhenyu Wang (Environmental Microbiology, 2009)
Summary The antibiotic‐resistance characteristics of bacterial strains in antibiotic production wastewater treatment plants (WWTP) that contain high concentrations of antibiotics are unknown, as are the environmental effects of the discharge of wastewater from such facilities. In this study, 417 strains were individually isolated from the effluent of a WWTP that treated penicillin G production wastewater, as well as from downstream and upstream areas of the receiving river. The minimum inhibition concentrations (MICs) of 18 antibiotics representing seven classes were then determined for each of these strains. Relatively high similarity in the bacterial composition existed between the wastewater and downstream river samples when compared with the upstream sample. High resistance ratios and MIC values were observed for almost all antibiotics in wastewater isolates, followed by strains from downstream river, of which the resistance ratios and levels were still significantly higher than those of upstream strains. The resistance ratios and levels also significantly differed among strains belonged to different species in the penicillin production wastewater effluent and downstream river. In both samples, the resistances to β‐lactam antibiotics were more frequent, with much higher levels, than the other class antibiotics. Then five clinically important resistant genes mainly coding for extended‐spectrum β‐lactamases (ESBLs) were determined for all strains, only bla TEM‐1 which did not belong to ESBL was detected in 17.3% and 11.0% of strains isolated from wastewater and downstream river respectively. Class I integrons were detected in 14% of wastewater isolates and 9.1% of downstream isolates, and primarily contained gene cassettes conferring resistance to aminoglycoside antibiotics. The unexpectedly high levels of multiple antibiotic resistance in strains from wastewater and downstream river were speculated to be mainly due to multidrug efflux systems.

Anti-angiogenesis effect of generation 4 polyamidoamine/vascular endothelial growth factor antisense oligodeoxynucleotide on breast cancer in vitro - Shan-zhi Gu; Xin-han Zhao; Ling-xiao Zhang; Li Li; Zhi-yu Wang; Min Meng; Gai-li An (Journal of Zhejiang University-SCIENCE B, 2009)

Linkage between mei-yu precipitation and North Atlantic SST on the decadal timescale - Wei Gu; Chongyin Li; Xin Wang; Wen Zhou; Weijing Li (Advances in Atmospheric Sciences, 2009)

A gain-of-function mutation of transcriptional factor PTL results in curly leaves, dwarfism and male sterility by affecting auxin homeostasis - Xin Li; Genji Qin; Zhangliang Chen; Hongya Gu; Li-Jia Qu (Plant Molecular Biology, 2008)

Molecular cloning and characterization of AAAS-V2, a novel splice variant of human AAAS - Xin Li; Chaoneng Ji; Jiefeng Gu; Jian Xu; Zhe Jin; Liyun Sun; Xianqiong Zou; Yun Lin; Ruping Sun; Peng Wang; Shaohua Gu; Yumin Mao (Molecular Biology Reports, 2005)

Cloning and characterization of a novel human phosphatidic acid phosphatase type 2, PAP2d, with two different transcripts PAP2d_v1 and PAP2d_v2 - Liyun Sun; Shaohua Gu; Yaqiong Sun; Dan Zheng; Qihan Wu; Xin Li; Jianfeng Dai; Jianliang Dai; Chaoneng Ji; Yi Xie; Yumin Mao (Molecular and Cellular Biochemistry, 2005)

Lipase-catalyzed naproxen methyl ester hydrolysis in water-saturated ionic liquid: significantly enhanced enantioselectivity and stability - Jia-Ying Xin; Yong-Jie Zhao; Yan-Guo Shi; Chun-Gu Xia; Shu-Ben Li (World Journal of Microbiology and Biotechnology, 2005)

Developmental analyses reveal early arrests of the spore-bearing parts of reproductive organs in unisexual flowers of cucumber (Cucumis sativus L.) - Su-Lan Bai; Yi-Ben Peng; Ji-Xin Cui; Hai-Tao Gu; Li-Yun Xu; Yi-Qin Li; Zhi-Hong Xu; Shu-Nong Bai (Planta, 2004)

Cloning and characterization of a human cDNA ACAD10 mapped to chromosome 12q24.1 - Xin Ye; Chaoneng Ji; Chun Zhou; Li Zeng; Shaohua Gu; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2004)

Characterization of a cDNA encoding a protein with limited similarity to β1, 3-N-acetylglucosaminyltransferase - Huarui Zheng; Yao Li; Chaoneng Ji; Jixi Li; Jiayi Zhang; Gang Yin; Jian Xu; Xin Ye; Maoqing Wu; Xianqiong Zou; Shaohua Gu; Yi Xie; et al. (Molecular Biology Reports, 2004)

Note: Isolation and Characterization of a Jerky and JRK/JH8 Like Gene, Tigger Transposable Element Derived 7, TIGD7 - Tonghai Dou; Shaohua Gu; Zongxiang Zhou; Chaoneng Ji; Li Zeng; Xin Ye; Jian Xu; Kang Ying; Yi Xie; Yumin Mao (Biochemical Genetics, 2004)

Characterization of a human Sec14-like protein cDNA SEC14L3 highly homologous to human SPF/TAP - Xin Ye; Chaoneng Ji; Gang Yin; Rong Tang; Li Zeng; Shaohua Gu; Kang Ying; Yi Xie; Robert Chunhua Zhao; Yumin Mao (Molecular Biology Reports, 2004)

cDNA cloning and expression analysis of a novel human F-box domain containing gene† - Li Zeng; Shaohua Gu; Yao Li; Wenhu Wang; Yan Huang; Xin Ye; Jian Xu; Enpeng Zhao; Chaoneng Ji; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2004)

Developing gene-tagged molecular markers for functional analysis of starch-synthesizing genes in rice (Oryza sativa L.) - Xinyan Liu; Minghong Gu; Yuepeng Han; Qing Ji; Jufei Lu; Shiliang Gu; Rong Zhang; Xin Li; Jianmin Chen; Schuyler S. Korban; Mingliang Xu (Euphytica, 2004)

Cloning and sequence analysis of the human cDNA encoding the synaptoporin (Δ), a highly conservative synaptic vesicle protein - Jianfeng Dai; Chaoneng Ji; Shaohua Gu; Qihan Wu; Liu Wang; Jian Xu; Li Zeng; Xin Ye; Gang Yin; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)

Isolation and characterization of a human putative receptor protein kinase cDNA STYK1* - Xin Ye; Chaoneng Ji; Qingshan Huang; Chao Cheng; Rong Tang; Jian Xu; Li Zeng; Jianfeng Dai; Qihan Wu; Shaohua Gu; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)

Molecular Cloning and Characterization of a Novel Human Hydroxysteroid Dehydrogenase-Like 2 (HSDL2) cDNA from Fetal Brain - Jianfeng Dai; Yi Xie; Qihan Wu; Liu Wang; Gang Yin; Xin Ye; Li Zeng; Jian Xu; Chaoneng Ji; Shaohua Gu; Qingshan Huang; Robert Chunhua Zhao; et al. (Biochemical Genetics, 2003)

Note: Isolation and Characterization of a Novel Human Putative Anemia-Related Gene Homologous to Mouse Sideroflexin - Xin Ye; Jian Xu; Chao Cheng; Gang Yin; Li Zeng; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Biochemical Genetics, 2003)

Cloning and characterization of a novel human STAR domain containing cDNA KHDRBS2* - Liu Wang; Jian Xu; Li Zeng; Xin Ye; Qihan Wu; Jianfeng Dai; Chaoneng Ji; Shaohua Gu; Chunhua Zhao; Yi Xie; Yumin Mao (Molecular Biology Reports, 2002)

Epoxypropane biosynthesis by Methylomonas sp. GYJ3: batch and continuous studies - Jia-Ying Xin; Jun-Ru Cui; Li-Min Zhu; Jian-Bo Chen; Chun-Gu Xia; Shu-Ben Li (World Journal of Microbiology and Biotechnology, 2002)

Cloning, expression and characterization of a novel human VMP gene* - Chao Cheng; Jian Xu; Xin Ye; Jianfeng Dai; Qihan Wu; Li Zeng; Liu Wang; Wei Zhao; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Molecular Biology Reports, 2002)

Alteration of N-acetylglucosaminyltransferases in pancreatic carcinoma - Bi-cheng Nan; Dong-min Shao; Hui-li Chen; Yong Huang; Jian-xin Gu; Yi-bin Zhang; Zhao-guang Wu (Glycoconjugate Journal, 1998)